Stable hydrogen (δ2H) and oxygen (δ17O and δ18O) isotopes reveal hydrodynamic water-mass structure and algal bloom susceptibility in the Three Gorges Reservoir: A machine learning-assisted analysis - Yaxin Zhu; Guilin Han; Di Wang; Yuchun Wang (Water Research, 2026)

Screening optimum reference genes for quantitative real-time polymerase chain reaction analysis in invasive apple snail, Pomacea canaliculata under different conditions - Ya-Wen Chang; Han-Di Long; Ran Wei; Zhen-Jun Sun; Guo-Xian Zha; Cheng-Dong Wu; Hong-Fang Xie; Jie Hu; Yu-Zhou Du (Molecular Biology Reports, 2026)

AI cold storage delays winter jujube aging and preserves flavor by regulating reactive oxygen metabolism and ethanol fermentation pathways - Yujiao Zhou; Yi Xiao; Yue Qiu; Xiangrui Cui; Ye Han; Yang Li; Baijun Li; Yilong Liu; Xiaoyong Zhao; Di Wu; Bo Zhang; Kunsong Chen; et al. (Postharvest Biology and Technology, 2026)

Interfacial reactivity and NaOL adsorption mechanisms on magnesite and calcite: Insights from surface complexation model - Xinzhuang Fu; Chuanxi Peng; Di Chen; Haisheng Han; Wei Sun; Tong Yue (Minerals Engineering, 2026)

Effects of sustained eccentric loading on concrete-encased concrete-filled steel tubular (CFST) columns - Zhi-Cheng Yang; Di Fan; Guan-Yuan Zhao; Li Zhu; Lin-Hai Han; Chen-Yu Zhang (Engineering Structures, 2026)

Lunar transient atmosphere recorded in Chang'e 6 impact glass beads - Ziyan Han; Hejiu Hui; Sen Hu; Zhiyong Xiao; Fanglu Luo; Di Zhang; Yutao Lin; Huicun He; Liang Gao; Yue Zhang; Wenxin Ouyang; Yu Li; et al. (Earth and Planetary Science Letters, 2026)

Mild amorphization and structural reconstruction enable non-destructive recycling of continuous fiber-reinforced PAEK composites - Zhongxin Dong; Yanchao Yang; Dianfu Ren; Yanwei Xiao; Di Wu; Liangliang Pei; Yunhe Xing; Han Feng; Shengdao Wang; Guibin Wang (Chemical Engineering Journal, 2026)

Electronegativity-guided d-band center tuning of MnFeCoNiCu high-entropy alloy: Boosting polysulfide conversion for high-performance lithium-sulfur batteries - Jingkun Ren; Yu Shao; Xitian Zhang; Fengfeng Han; Di Wang; Qi Jin; Tong Qi; Zhihao Liu; Jing He; Xinzhi Ma; Lili Wu (Chemical Engineering Journal, 2026)

AI-accelerated discovery of a high-entropy garnet electrolyte with a flattened Li-ion energy landscape for practical solid-state batteries - Liming Wang; Kehao Tao; Qingmei Su; Weihao Shi; Di Han; Shaochen Wei; Wenxin Shi; Xuan Li; Huayu Li; Gaohui Du; Wenqi Zhao; Miao Zhang; et al. (Chemical Engineering Journal, 2026)

Elemental profiles and determinants of hair composition in residents of Nanning, China: insights from multivariate and comparative analyses - Ziyang Ding; Guilin Han; Hongcheng Mei; Rui Qu; Di Wang; Wenqian Sun; Na Mi; Jun Zhu (ENGINEERING Environment, 2026)

Efficacy and durability of therapies for neurogenic lower urinary tract dysfunction: A network meta-analysis of Botulinum Toxin a, instillations, and neuromodulation - Beibei Lei; Cunyu Lan; Yage Wang; Shenhong Ma; Heling Wang; Di Zhang; Qiaohua Han; Weisheng Zhuang (Toxicon, 2026)

Sustainable maritime emergency resources in oil spill accidents: a multi-objective optimization under uncertainty - Bin Han; Yuanjun Feng; Shiqi Fan; Di Zhang (Ocean Engineering, 2026)

Rare earth element profiles and fractionation patterns in modern human dental enamel from Beijing, China - Lisheng Zhao; Xiaoyu Hu; Guilin Han; Di Wang; Wenqian Sun; Xi Gao (Journal of Trace Elements in Medicine and Biology, 2026)

A green ferrofluid based on hydrated deep eutectic solvent for dispersive liquid-liquid microextraction of bisphenols from edible oil - Jiangping Cao; Zetong Wang; Chongchong Du; Xueli Zhuang; Jimei Zhou; Juanjuan Wei; Hongwei Di; Yangying Han (Food Chemistry, 2026)

β-Cyclodextrin-mediated co-encapsulation of peptide PPHG and gallic acid: Synergistic thrombin-inhibitory activity, enhanced stability, and sustained simulated gastrointestinal release - Zi-Han Qu; Zi-Han Liu; Xue-Fu Li; Hai-Bin Ren; Di-Feng Ren; Jun Lu (Food Bioscience, 2026)

In-Season monitoring of rice phenology for massive germplasm resources using Explainable Machine learning and a Transformer CNN model - Xiaoxu Han; Yangyang Gu; Hengbiao Zheng; Di Wang; Fangming Wu; Meng Zhou; Hongxu Ai; Timothy A. Warner; Chongya Jiang; Tao Cheng; Yongchao Tian; Yan Zhu; et al. (Computers and Electronics in Agriculture, 2026)

Stage-resolved zinc isotope dynamics in firefighters’ hair after firefighting - Ziyang Ding; Guilin Han; Qian Zhang; Rui Qu; Jian Hu; Di Wang; Wenqian Sun; Ye Zhao (Journal of Hazardous Materials, 2026)

From dark-brown to yellow: metabolomics reveals ROS alterations regulating glutathione metabolism to control cap color changes in Flammulina filiformis - Xinmin Liang; Jing Han; Tianhai Liu; Yang Yu; Di Wang; Bo Wang; Dinghong Jia; Weihong Peng; Xiaolan He; Xun Liu (Food Research International, 2026)

Liquid-filled stick microextraction with in situ derivatization: An efficient tool for the quality control of herbal products targeting α-dicarbonyl compounds - Dong Wang; Mengrong Li; Yuanyuan Zheng; Xiangyu Zhang; Lifeng Han; Di Chen (Food Chemistry, 2026)

Distinct contributions of the peroxisomal import receptors CgPEX5 and CgPEX7 in regulating fungal growth, conidia development, and pathogenicity of the Colletotrichum gloeosporioides - Zhanhong Han; Dandan Ren; Pinkuan Zhu; Di Gong; Zhengke Zhang; Yonggui Pan (Food Microbiology, 2026)

Geochemical and microbial functional responses of surface soil to simulated low-concentration CO2 leakage from geological storage - Junqing Sun; Xiaoyu Han; Xiaojun Sun; Huaxiu Qin; Di Yang; Mohan Shangguan; Jinren Lu; Haoshuai Li; Yang Li; Mutai Bao (Environmental Research, 2026)

Curdlan-mangiferin composite hydrogel encapsulating coenzyme Q10 alleviates dry eye disease by improving mitochondrial function - Wenshuo Han; Yaning Liu; Huanhuan Ge; Hanwen Guo; Xinqi Zhao; Zijian Gao; Guohu Di; Xianggen Wu; Lei Tian; Peng Chen; Xiaoping Zhang (Chemical Engineering Journal, 2026)

Dual-clay composite electrolyte with rigid-flexible interlocked architecture for safe lithium metal batteries - Zhangkuo Han; Shusen Zhou; Di Jiang; Jiahan Zheng; Huiying Hao; Jie Xing; Jingjing Dong; Hao Liu; Libing Liao (Chemical Engineering Journal, 2026)

Photothermal Agents in Cancer Therapy: Applications and Development Prospects - Shiyu He; Shuaipeng Feng; Yiming Han; Qingqing Xu; Jiaru Lan; Donghua Di; Da Wang; Siling Wang; Huan Zhai; Qinfu Zhao (Chemical Engineering Journal, 2026)

The coevolution of climate-social and ecological systems in the Anthropocene: evidence from lake sediment records - Di Wen; Wenxiang Zhang; Qiushi Liang; Qiaohua Han; Jiqing Yin; Tian Wu; Xianglei Yang; Mengyang Han; Taohui Li (CATENA, 2026)

A novel artificial component air ventilation system for thermal environment and air quality control in underground refuge chamber - Baoyun Bu; Angui Li; Changqing Yang; Shengjie Di; Ying Zhang; Han Luo; Jing Xiong (Building and Environment, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Rare Earth Element and Yttrium Fingerprints in Human Kidney Stones: Tracing Environmental Exposure and Pathological Mineralization Pathway - Di Wang; Guilin Han; Chaochun Fu; Wenqian Sun; Ziyang Ding; Haibo Li (Biological Trace Element Research, 2026)

Nicotinic acid enhances heavy metal stress resilience of wastewater anammox communities via NAD+ replenishment - Min Xu; Shiyi Han; Xiaoxin Cao; David S. Ikumi; Di Wu; Changzhi Wang; Huijie Lu (Water Research, 2026)

Engineering heterostaple in atomically precise palladium cluster for efficient hydrogen peroxide electrosynthesis - Jiachun Li; Yan Sun; Min Du; Shuguang Wang; Baoliang Han; Jiacheng Wang; Xiaoyi Yang; Fangkai Wu; Fuling Liu; Xiaofeng Lei; Afang Dai; Zibao Gan; et al. (Science Bulletin, 2026)

Numerical investigation of dynamic response of HDPE raft-cage aquaculture systems under combined wave-current conditions: Multi-System coupling analysis - Fei Fu; Xiaoying Zhang; Zhanbin Meng; Di Ren; Xiangxi Han; Jianxing Yu; Zhe Hu (Ocean Engineering, 2026)

Gill dysfunction and metabolic disruption: the size-dependent effects of microplastics on Chiromantes haematocheir - Yijuin Tay; Ji Liang; Yuanhao Yang; Di Ren; Xingkong Ma; Mengyu Bao; Zihan Zhou; Mingming Han; ZhenChao Li; Anisah Lee Binti Abdullah; Tianheng Gao; Qichen Jiang (Marine Environmental Research, 2026)

Simultaneous leaching of Li, Rb, Cs from lepidolite via external electric field enhanced alkali leaching - Kun Xu; Mingming Yu; Heyue Niu; Yusufujiang Mubula; Zhehan Zhu; Di Han; Jingzhong Kuang; Lingguo Meng; Guichun He (Minerals Engineering, 2026)

Soy-whey dual-protein alleviates muscle atrophy in lung cancer cachexia by regulating the FoxO/MuRF-1/Atrogin-1 signaling pathway - Na Li; MengJie Li; Duo Feng; Di Han; Hu Li; Jiayu Fan; Ruiqi Xu; Jing Wang (Food and Humanity, 2026)

Immune interventions in stroke: current progress and perspectives - Cunle Guo; Di Guan; Qiang Liu; Zhaoli Han (Science China Life Sciences, 2026)

Modern human dental enamel as a biomineral baseline for rare earth elements and yttrium in urban Nanjing, China - Xiaoyu Hu; Lisheng Zhao; Ziyang Ding; Xi Gao; Di Wang; Wenqian Sun; Biao Zhu; Guilin Han (Environmental Geochemistry and Health, 2026)

Integrated deep learning and multi-scale modeling for the discovery of pan-genotypic HCV NS5B polymerase inhibitors - Di Han; Fengxiang Liu; Xiangbing Peng; Yifan Wang; Zhipeng Shi; Yiwei Xue; Hongkun Yang; Meiting Wang; Jiarui Lu; Taigang Liu; Shaoli Cui; Yongtao Xu (Molecular Diversity, 2026)

Parvimonas micra is a specifically enriched bacterium in advanced canine periodontal disease and its effects are ameliorated using ADSCs-exosomes - Miao Yu; Zheng Wang; Xiao Han; Yansong Ge; Zijian Geng; Jianfa Wang; Di Wang; Shuai Lian (Veterinary Microbiology, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Experimental study on the characteristics of vortex-induced vibrations of a two-degree-of-freedom cylinder near a wall at high Reynolds numbers - Junlong Su; Xiangxi Han; Haonan Guo; Yunfu Liu; Fenjie Pei; Shuwen Wang; Di Ren; Zhanbin Meng; Dan Chen (Ocean Engineering, 2026)

Anomalous contaminant transport in fractured porous media: Insight from asynchronous hydraulic changes in fractures and rock matrix - Lei Ma; Di Han; Qiankun Luo; Yaping Deng; Yunhai Fang; Chao Zhang; Jiazhong Qian (Journal of Contaminant Hydrology, 2026)

Microfluidic-based magnetic microspheres for targeted delivery of curcumin nanoparticles in gastroesophageal reflux disease therapy - Haoyao Jiang; Zhonglin Fang; Han Lin; Di Xu; Wanqian Xu; Mengqi Han; Luoran Shang; Ye Zhao; Teng Ma; Di Ge (Chemical Engineering Journal, 2026)

Endophytic bacteria modulate rhizosphere microbiota and nitrogen transformations in Paulownia fortunei (Seem.) Hemsl - Han Ren; Furong Luo; Baoling Huang; Yufan Luo; Tongbao Zhang; Zhiyuan Wang; Yinghao Guo; Di Xu; Chengqun Lv (Plant and Soil, 2026)

Baseline and fractionation of rare earth elements in hair of urban residents in Nanning, South China - Hongcheng Mei; Ziyang Ding; Guilin Han; Rui Qu; Xiaoyu Hu; Di Wang; Zhaowei Jie; Wenqian Sun; Jun Zhu (Environmental Geochemistry and Health, 2026)

Methane emissions under vegetation succession regulated by soil conditions and microbes in Yellow River Delta wetlands - Yunxuan Han; Linhui Ji; Yu Xin; Zihao Wang; Xia Gao; Lei Yu; Dufa Guo; Hongjie Di; Xiaoya Xu (Applied Soil Ecology, 2026)

A calculation model on the minimum safe thickness of water-resisting rock mass for tunnel crossing active fault considering the fractal dimension and seismicity - Fan-meng Kong; Bing-hua Zhou; Xin Li; Zhao-di Han; Wen-song Wang (Applied Geophysics, 2026)

An integrated assessment model for indoor environmental quality performance and passenger satisfaction in metro carriages - Chao Li; Song Pan; Chunqing Wang; Mingyuan Qin; Xinru Wang; Yongji Wang; Di Han; Yaohua Zhao (Tunnelling and Underground Space Technology, 2026)

Experimental and NDEM investigation of resistance and pressure statistics of an inclined plate interacting with broken ice - Ziwang Chen; Baoyu Ni; Shaocheng Di; Yanzhuo Xue; Xuchen Ren; Bowen Han (Ocean Engineering, 2026)

Bimetallic metal-organic frameworks-modified hybrid capacitive deionization for enabling concurrent desalination and antibiotic resistance genes removal - Ziwei Chen; Zhanming Tan; Xuefeng Liu; Peilin Han; Di Zhang; Mengqi Jiang; En Xie; Yunkai Li (Desalination, 2026)

Polyphenol-tailored dandelion-like Janus nanomotors synchronizing catalytic immunomodulation and osteochondral regeneration for rheumatoid arthritis therapy - Haohua Ma; Di Liu; Wenxiu Hu; Jinguang Yang; Pengfei Cui; Lu Han (Chemical Engineering Journal, 2026)

Polyphenol-tailored dandelion-like Janus nanomotors synchronizing catalytic immunomodulation and osteochondral regeneration for rheumatoid arthritis therapy - Haohua Ma; Di Liu; Wenxiu Hu; Jinguang Yang; Pengfei Cui; Lu Han (Chemical Engineering Journal, 2026)

Research on diffusion characteristics and parameters of artificial component air ventilation in underground refuge chamber - Baoyun Bu; Angui Li; Changqing Yang; Shengjie Di; Ying Zhang; Han Luo (Building and Environment, 2026)

Discovery of cold tolerance genes and favorable alleles in Kam sweet rice across various growth stages - Kunchi Yu; Chunhui Liu; Joohyun Lee; Xiaoding Ma; Bing Han; Zhengwu Zhao; Soon-Wook Kwon; Longzhi Han; Di Cui (Theoretical and Applied Genetics, 2026)

Rapid intensification of western north pacific tropical cyclones features more concentrated onset for September and slower translation - Huichao Tian; Di Tian; Han Zhang; Feng Zhou (Climate Dynamics, 2026)

Standardized ready-to-use natural deep eutectic solvent-impregnated polypropylene fiber units for robust and high-throughput determination of tyrosine kinase inhibitors in biological fluids - Dong Wang; Mengrong Li; Xiangyu Zhang; Xu Miao; Lifeng Han; Di Chen (Analytica Chimica Acta, 2026)

Source identification and coastal export of sulfate in a megacity river: Insights from sulfur isotopes and inverse model - Xuehui Liu; Guilin Han; Jinke Liu; Jie Ren; Xi Gao; Di Wang (Marine Pollution Bulletin, 2026)

Dynamic response mechanism of mooring forces on a ship-type buoy under the coupled action of landslide-generated impulse waves and currents - Pingyi Wang; Lu Hua; Linfeng Han; Ye Tian; Di Song; Shanchuan Zhe (Ocean Engineering, 2026)

Persulfate-based advanced oxidation processes enhanced biomass carbon activation efficiency for high-performance supercapacitors - Tao Zhang; Hongkai Di; Hanrui Ma; Guangzhe Zhang; Kunjie Li; Ruihong Zhao; Wentao Niu; Jiangze Han; Jingsi Yang (Fuel, 2026)

Effects of eugenol on physiological metabolism and nutritional quality of Chinese mitten crab (Eriocheir sinensis) during simulated cold chain logistics process - Jingyi Han; Yuyao Shi; Junlin Zhu; Di Sun; Wenzheng Shi; Changhua Xu; Xichang Wang; Mingyu Yin (Food Chemistry, 2026)

An integrated strategy from enhanced production to functional delivery: astaxanthin enrichment via Xanthophyllomyces dendrorhous fermentation and antioxidant evaluation of its two loaded particles - Yuan-Yuan Li; Jun An; Yi-Han Wang; Wei Xiao; Lan-Xin Qian; Di-Feng Ren (Food Bioscience, 2026)

Hydrogen sulfide maintains banana postharvest quality by antagonizing ethylene and enhancing antioxidant properties in Musa nana Lour - Xue-Ting Cheng; Yan-Hong Li; Yun Ge; Zhuo Han; Yi-Ang Feng; Ying-Zhi Zhang; Kang-Di Hu; Gai-Fang Yao; Pedro García-Caparros; Hua Zhang (Food Control, 2026)

Synergistic catalytic mechanism of constituent metal atoms in high−entropy alloy catalysts for Li − S batteries - Tong Qi; Yu Shao; Chi Zhang; Di Wang; Fengfeng Han; Qi Jin; Zhihao Liu; Xitian Zhang; Lu Li; Lili Wu (Chemical Engineering Journal, 2026)

Efficient ultraviolet emission via Ce3+-doped lead-free double perovskite nanocrystals for multicolor and full-spectrum luminescence - Zewen Wang; Xiaowei Deng; Xu Chen; Weilong Qin; Meng Wang; Yongjie Zai; Mochen Jia; Ying Liu; Zhuangzhuang Ma; Jibin Zhang; Linyuan Lian; Yanbing Han; et al. (Chemical Engineering Journal, 2026)

The impact of radiative cooling paint on a factory building in tropics - Di Han; Yongping Long; Man Pun Wan; Bing Feng Ng (Building and Environment, 2026)

A Study on the Response of Monopile Foundations for Offshore Wind Turbines Using Numerical Analysis Methods - Zhijun Wang; Di Liu; Shujie Zhao; Nielei Huang; Bo Han; Xiangyu Kong (Journal of Marine Science and Engineering, 2026)
The prediction of dynamic responses of offshore wind turbine foundations under wind-wave-current multi-field coupled loads is the cornerstone of safety in offshore wind power engineering. The currently widely adopted equivalent load application method, while computationally efficient, simplifies loads into concentrated forces applied at the pile top and tower top, neglecting fluid-structure dynamic interaction mechanisms, which leads to deviations in response predictions. To overcome this limitation, this paper proposes a high-precision bidirectional fluid-structure interaction numerical framework. The fluid domain employs computational fluid dynamics (CFD) to construct an air-seawater two-phase flow model, utilizing the standard k-ε turbulence model and nonlinear wave theory to accurately simulate complex marine environments. The solid domain establishes a wind turbine-stratified seabed system via the finite element method (FEM), describing soil-rock mechanical properties based on the Mohr-Coulomb constitutive model. Comparative studies indicate that the equivalent static method significantly underestimates the displacement response of pile foundations, particularly under the extreme shutdown conditions examined in this study. This value should be interpreted as a case-specific observation rather than a universal deviation, and the discrepancy may vary with sea state, wind speed, current velocity, and wind–wave misalignment, thereby leading to non-conservative estimates of stress distribution. In contrast, the fluid-structure interaction method can reveal key physical processes such as local flow acceleration and wake–interference effects around the tower and the parked rotor under shutdown conditions, and the nonlinear interaction and resistance-increasing mechanisms between waves and currents. This model provides a reliable tool for safety assessment and damage evolution analysis of wind turbine foundations under extreme marine conditions, promoting the transformation of offshore wind power structure design from empirical formulas to mechanism-driven approaches.

Anthropogenic gadolinium anomalies and reservoir-driven removal of dissolved rare earth elements in the world's largest hydropower project - Di Wang; Guilin Han; Yuchun Wang; Shunrong Ma (Water Research, 2026)

Numerical study of the effect of the pitch ratio of a helical strake on the vortex-induced vibration of a cylinder - Xiumei Ling; Xiangxi Han; Junlong Su; Hongqi Luo; Jiahao Zhang; Liping Fang; Zhanbin Meng; Youhong Tang; Di Ren (Ocean Engineering, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Metabolomics-based reveals the relation between internal metabolism and storage quality of sesame harvested by machine at different speeds - Ling-Yu Qu; Shu-Guang Gao; Di-Chen Gong; Jing-Wen Zhao; Yun-Xuan Hu; Xiao-Tian Zhu; Han-Zhe Zhang; Hua-Min Liu; Hong-Mei Miao (Food Research International, 2026)

Deciphering the mechanisms underlying cadmium tolerance in the endophytic fungus Trichoderma atroviride D16 - Xue-Wen Bi; Xing-Guang Xie; Wen-Jing Zhang; Rui-Di Zhang; Khalid Rahman; Xin-Zhu Yu; Cun-Yu Fan; Shu-Lang Ding; Yu-Qing Peng; Ting Han (Fungal Biology, 2026)

Hydrothermal carbonization of pharmaceutical sludge in ecological engineering: Optimizing carbon structure for sustainable fuel-grade hydrochar and bioenergy recovery - Wang Liang; Yihao Cui; Yihan Chen; Di Zhu; Yonghui Han; Chunhe Jiang; Yali Huang; Xiaojun Ning; Chuan Wang; Guangwei Wang (Biomass and Bioenergy, 2026)

Efficient mitochondrial DNA editing in rabbits with engineered sTALED base editors - Di Wang; Yuqiang Qian; Wenchao Niu; Heng Gong; Ding Zhao; Xun Gao; Deqiang Kong; Jiale Zhou; Yang Han; Liangxue Lai; Zhanjun Li (Science China Life Sciences, 2026)

The Regulating Effect of Weizmannia coagulans BC-G44 on Antibiotic-Associated Diarrhea and its Improvement on Gut Microbiota - Zhouyi Wang; Yinghan Xiang; Yafang Xu; Jiaxin An; Qianrui Wei; Yang Chen; Di Han; Zhanxi Hao; Huajun Li (Probiotics and Antimicrobial Proteins, 2026)

An integrated strategy for the efficient extraction and stabilization of phycocyanin from Limnospira platensis - Yuan-Yuan Li; Zhen-Wei Shi; Sheng-nan Yin; Hai-Bin Ren; Zi-Han Qu; Di-Feng Ren (Journal of Applied Phycology, 2026)

Emergence of a KL239-OCL6-ST63 Carbapenem-Resistant Acinetobacter pittii Strain, Co-carrying blaNDM-1 and blaOXA-500 - Di Zhou; Jiayi Fan; Duo Zhang; Xiaohan Ma; Yifei Li; Xindan Zhang; Shuai Zheng; Qinlong Hou; Shuang Li; Gen Li; Huiming Han (Current Microbiology, 2026)

Global Warming Amplifies Nitrogen Over Phosphorus Limitation in Aquatic Ecosystems: A Multi‐Trophic Meta‐Analysis - Misha Zhong; Ping Xie; Yuhao Feng; Wenxuan Han; Enzai Du; Di Tian; Ruijing Ma; Yuwei Wang; Zengliang Jian; Jianfeng Chen; Qingyang Rao; Shangsheng Sun; et al. (Global Change Biology, 2026)
Nitrogen (N) and phosphorus (P) availability fundamentally regulate the structure and function of aquatic ecosystems. While global‐scale patterns of relative nutrient limitation have been increasingly documented, their responses to climate warming remain poorly quantified. To address this, we integrated a global meta‐analysis of nutrient enrichment experiments (spanning 510 sites and multiple trophic levels) with large‐scale datasets of water chemistry from 3403 lakes and 13,032 marine sites. Meta‐analysis showed that primary producers have the strongest responses to nutrient enrichment, especially NP co‐addition, with effects attenuating at higher trophic levels. Increasing temperature amplifies the response of primary producers to nutrient enrichment, but not for consumers, indicating that warming disrupts energy flow to higher trophic levels. Furthermore, relative N limitation of primary producers intensifies with increasing temperature and decreasing latitude in both freshwater and marine ecosystems. Global field observation of water chemistry supports such a pattern as water N:P mass ratios decrease with increasing temperature across lake and marine ecosystems. Our findings provide robust empirical evidence that the relative nutrient limitation of primary producers exhibits a strong latitudinal gradient and climate warming could fundamentally enhance nitrogen over phosphorus limitation in aquatic ecosystems, which have critical implications for ecosystem functioning and management in a warmer world.

Tu-Si-Zi-Wan reduces D-galactose-induced hepatic and cerebral oxidative damage in aging mice via the Nrf2/ARE pathway - Guoping He; Di Wu; Juanjuan Wang; Lei Zhang; Chunyan Zhang; Xiaozhi Liu; Xiangli Han (Metabolic Brain Disease, 2026)

DBH-YOLO: A novel algorithm for surface defects detection of postharvest blue honeysuckle berry fruit - Liangliang Xue; Hongyue Cong; Di Xu; Jingxin Han; Haoran Wang; Chenghai Liu; Xianzhe Zheng (Postharvest Biology and Technology, 2026)

Specific anrA primers uncover microbial antimony reduction and community dynamics in contaminated environments - Jun-Lu Lv; Di Min; Dong-Feng Liu; Han-Qing Yu (Journal of Hazardous Materials, 2026)

Revealing hydrodynamic controls on algal bloom outbreaks in the Three Gorges Reservoir backwater area: Insights from triple oxygen isotopes analysis - Yaxin Zhu; Di Wang; Yuchun Wang; Guilin Han (Journal of Environmental Management, 2026)

Corrigendum to “MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting” [Chem. Eng. J. 525 (2025) 170080] - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2026)

In situ formation of chylomicron-incorporated lipid nanoparticles via muramyl dipeptide conjugation potentiates lymphatic transport of chemoimmunotherapeutic for leukemia therapy - Pengbo Zhao; Yu Ding; Yinyin Yuan; Huanyu Qin; Jinyu Dai; Di Wu; Zhenduo Duan; Lihui Xin; Luojuan Hu; Sifei Han; Xiaofei Xin; Lifang Yin (Chemical Engineering Journal, 2026)

Divergence or Convergence? A Comparison of InVEST and SWAT in Simulating Water Conservation Patterns and Drivers - Li Ma; Jianling Yang; Yingjuan Han; Zhenhua Di; Xueyi Zhang; Yazhen Wu; Liping Ma; Xuemei Yang (Water Resources Management, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

One-step phase separation and magnetic retrieval of switchable natural deep eutectic solvents via Fe3O4@CA composites for rapid extraction of illegal non-steroidal anti-inflammatory drugs in herbal extracts - Jin-Yue Dong; Rong-Jie Wang; Qing Ran; Xiao-Bei Yang; Wen-Chao Han; Feng-Qi Dong; Di Chen (Sustainable Chemistry and Pharmacy, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

wViP: an online server of word cloud visualization of biological profiles - Jianzhen Peng; Miaomiao Chen; Xinhe Huang; Cheng Han; Di Peng; Yu Xue (Science Bulletin, 2026)

Event-triggered Bayesian optimization-based MPC-SMC framework for motion control of offshore fishing underwater vehicles: Simulation validation and experimental investigation - Han Bao; Yanyan Wang; Jing Liu; Di Liu (Ocean Engineering, 2026)

Bacterial assembly and succession during aerobic granulation stimulated by Fe3O4 nanoparticles with real municipal wastewater: The role of acyl-homoserine lactones mediated communication - Kailing Pan; Caixia Fang; Yuxuan Wei; Hengyuan Zhang; Di Wu; Jiazhong Zhou; Wenjie Han; Xiaoyan Fan; Ling Wang; Shujuan Huang; Xuejun Bi (Journal of Water Process Engineering, 2026)

Heuristic resistance-driven graph approach for preferential flow pathway identification in 3D discrete fracture networks - Lei Ma; Jixian Li; Yaping Deng; Di Han; Haichun Ma; Xuelin Cui; Jiazhong Qian (Journal of Hydrology, 2026)

Unveiling the molecular mechanisms of dihydromyricetin regulating the biosynthesis of three key secondary metabolites in Monascus purpureus HBSD08 through integrated transcriptomic and metabolomic analyses - Ran Fang; Yingying Wang; Jie Qiao; Di Wu; Qianyu Gao; Chunzheng Han; Penghui Sun; Wanting Wang; Xin Zeng; Bingyue Xin; Biao Zhang; Deyin Zhao; et al. (Food Bioscience, 2026)

Lower thermal conductivity promotes high-efficiency thermoelectric power generation in n-type Bi2(Te, Se)3 - Fudong Zhang; Hu Zhang; Mingrui Zhang; Bohao Han; Mengqi Li; Beiquan Jia; Zhanhui Peng; Xiaolian Chao; Lingling Wei; Zupei Yang; Di Wu (Chemical Engineering Journal, 2026)

Phytochemical characterization and multi-target mechanism of Gleditsia sinensis Fructus in lung adenocarcinoma treatment - Zhengyuan Fan; Di Han; Tingting Shen; Ya Li; Suxiao Liu; Suyun Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

Global patterns and drivers of canopy storage capacity in different biomes - Meng-Di Wu; Zhi-Yun Jiang; Si-Yi Zhang; Yu-Jun Ma; Shui-Xia Li; Shu-Qin Han; Jin-Zhao Liu (Agricultural and Forest Meteorology, 2026)

Elaborating PFAS characteristics for Chinese electroplating industry by target and nontarget analysis - Bo-Xuan Zhang; Xiang-Zhou Meng; Bao-Cang Han; Zhen Zhao; Qin-Wen He; Cun-Di Ma; Qinghe Zhu; Jie Yang; Haiyan Qin; Yawei Wang (Water Research, 2025)

Effect of PEDV infection on IPEC-J2 cells on miR-328–3p/FoxO4/NF-κB/MLCK signaling axis - Yiming Wei; Zixuan Qi; Yaping Shuai; Shihui Zhao; An Liu; Jiuyuan Liu; Di Bao; Han Zhao; Shuang Zhang; Hongze Shao; Shushuai Yi; Jiangting Niu; et al. (Veterinary Microbiology, 2025)

Recharge mechanisms and evaporation mode of urban river in North China: Implications from triple oxygen isotopes - Yaxin Zhu; Guilin Han; Di Wang (Urban Climate, 2025)

Apple polyphenols inhibit the growth, development and pathogenicity of Colletotrichum gloeosporioides by regulating the peroxisome and autophagy pathways - Zhanhong Han; Di Gong; Yue Xiang; Jialiang Liu; Hanyue Yang; Yaxin Tan; Hanchi Guan; Song Wu; Yonggui Pan; Zhengke Zhang (Postharvest Biology and Technology, 2025)

Late Ediacaran to early Cambrian tectono–depositional pattern of the western upper Yangtze Block, SW China: Implications for the break–up of the Pannotia supercontinent - Jinmin Song; Xin Jin; Zhiwu Li; Benjian Zhang; Lingli Zhao; Yi Ding; Di Yang; Yuehao Ye; Han Wang; Haoshuang Deng; Bin Wang; Jiamin Xue; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Contrasting geochemistry of apatite from the Jurassic W- and Sn-mineralized granites in the Qitianling field, Nanling Range, South China - Hongfei Di; Yong-Jun Shao; David Chew; Rui-Chang Tan; Han Zheng; Yong Liang; Wen-Jie Fang; Yi-Qu Xiong (Lithos, 2025)

Coral-like cobalt/nitrogen-doped porous carbon synergized with MnO₂ for ultrasensitive electrochemical detection of luteolin in floral teas - Yafeng Jin; Fangming Han; Didi Tong; Xinyue Song; Di Wang; Tao Wang; Xiangquan Qin; Na Chen; Xiaobo Li; Guangri Xu (Food Chemistry, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Lattice-confined single-atom Fe tunes co spin states for fast sulfur redox in Li S batteries - Baihui Chen; Chunkai He; Ye Tao; Di Wang; Hongrui Wu; Han Wang; Yaozu Jia; Xinzhi Ma; Lili Wu (Chemical Engineering Journal, 2025)

MXene-enhanced multifunctional hydrogel for ultrasensitive strain sensing and self-powered triboelectric energy harvesting - Zishuo Li; Liping Zeng; Peiyao He; Di Wu; Shuaiyuan Han; Yongtao Yao; Dawei Zhang; Likun Gao; Jianing Zhao; Pengfei Huo (Chemical Engineering Journal, 2025)

DNA-assembled architectures for multi-enzyme cascades in high-performance biosensing - Yu Fu; Miao Zhang; Jiaying An; Qingxiang Zhang; Yujie Yu; Han Zhang; Yuxin Si; Di Zhang; Yuxin Fang (Chemical Engineering Journal, 2025)

Recent progress in ternary group VI transition metal dichalcogenides: Preparation strategy, properties, and applications - Xiao-Yu Chen; Yuan Zhao; Zi-Han Liu; Yi-Tong Pang; Di-Gen Wei; Chen-Jing-Yi Wang; Cheng-Bao Yao (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

Botulinum Toxin A (BTA) for pain and function improvement in osteoarthritis: a systematic review and meta-analysis of clinical efficacy evidence from randomized controlled trials - Beibei Lei; Weisheng Zhuang; Yage Wang; Shenhong Ma; Heling Wang; Di Zhang; Qiaohua Han; Xu Wang; Qixin Ding; Yuefang Li (Toxicon, 2025)

Cyanoalanine Synthase encoding gene SlCAS1 regulates tomato fruit ripening by modulating pigment metabolism and ethylene biosynthesis - Song-Li Han; Yu-Qi Zhao; Li-Xia Li; Pedro Garcia-Caparros; Yan-Hong Li; Zhen Wang; Yi-Ang Feng; Kang-Di Hu; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Cardiorespiratory benefits of reducing indoor particulate matter depend on immune improvements: Insights into individual heterogeneity from a randomized, double-blind crossover trial - Aojing Han; Wenlou Zhang; Luyi Li; Di Yang; Yetong Zhao; Qisijing Liu; Wanzhou Wang; Shan Liu; Xuezhao Ji; Xiaoming Shi; Jing Huang; Shaowei Wu; et al. (Journal of Hazardous Materials, 2025)

Bidirectional regulation of carbon dioxide hydrate formation kinetics by sodium chloride and kinetic promoters: Unraveling the dual promotion-inhibition mechanism - Zhongsheng Wang; Zhaohui Zhou; Zhiming Liu; Lu Han; Xinyuan Zou; Guiyang Ma; Di Ao; Yue Qin; Meng Du (Journal of Cleaner Production, 2025)

Enhancement of soil organic matter stability cross-linked with aluminium drove the reallocation of ROSs for the directional oxidation of petroleum hydrocarbons - Xiumin Li; Yonghua Zhao; Hongliang Du; Di Han; Na Wang (Journal of Environmental Management, 2025)

Synchronously enhanced charge transfers and energy conversion performance of Co-MoSe2 via in situ doped and surface-functionalized design - Zi-Han Liu; Xiao-Yu Chen; Yuan Zhao; Yi-Tong Pang; Di-Gen Wei; Jing-Yi Wangchen; Cheng-Bao Yao (Chemical Engineering Journal, 2025)

One-step dual-functional modification of Ni-rich cathodes via DFT prediction for high-rate quasi-solid-state batteries - Yunting Wang; Gaohui Du; Di Han; Weihao Shi; Liming Wang; Libing Yao; Huayu Li; Jingyi Jing; Shaochen Wei; Shixian Chen; Wenqi Zhao; Qingmei Su (Chemical Engineering Journal, 2025)

Root colonization by Serendipita indica triggers resistance against stem rot in Arachis hypogaea L - Ao Ding; Taswar Ahsan; Di Han; Chen Wang; Sitong Du; Wenrui Wang; Bingbing Liang; Chaoqun Zang; Yuqian Huang; Shihong Zhang (World Journal of Microbiology and Biotechnology, 2025)

α-Synuclein Pathology from Kidney to Brain in Parkinson’s Disease - Yihang Han; Yanjuan Wang; Yunnan Lu; Chunming Xie; Di Wu (Neuroscience Bulletin, 2025)

NxO emission from a pure-MBBR system: Characteristics, influencing factors, bacterial community, and metabolism pathway - Xing Fan; Jianchang Wang; Xuyi Wang; Di Wu; Haicheng Liu; Xiaolin Zhou; Shujuan Huang; Jiazhong Zhou; Wenjie Han; Xiaoyu Liu; Tang Yang; Xuejun Bi (Journal of Environmental Chemical Engineering, 2025)

Reflections of tropical cyclone-generated near-inertial internal waves within an anticyclonic eddy in the southern Bay of Bengal - Yingyu Peng; Di Tian; Feng Zhou; Han Zhang; Shengming Yuan; Zifei Chen; Ruijie Ye (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Z-scheme TiO2@CeO2 nanozyme/sonodynamic combination therapy for breast cancer by immunomodulation of tumor microenvironment - Renyu Liu; Wei Wang; Chengcheng Zhang; Liangfang Shen; Rongrong Zhou; A'meng Han; Di Jing; Zijian Zhang; Xianbo Wu; Liu Deng; You-Nian Liu; Xin Zhang (Chemical Engineering Journal, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Cobalt-doped Bi2Fe4O9 nanosheets effectively enhance peracetic acid activation for sulfamethoxazole degradation: Performance and mechanism - Songyun Liu; Zhan Lian; Qi Yu; Guang Wang; Fei Di; Fangfang Ma; Donghui Han (Chemical Engineering Journal, 2025)

Late-Stage Activation of Toll-like receptor 3 Alleviates Cognitive Impairment and Neuropathology in an Alzheimer’s Disease Mouse Model - Taiyang Zhu; Fanyu Shen; Xiao Jia; Hui Zhou; Wanyan Ni; Shang Wang; Di Wu; Huimin Gao; Zhenying Shang; Yan Zhou; Jingjing Han; Guoliang Jin; et al. (Molecular Neurobiology, 2025)

Integrated source apportionment and risk assessment prioritizes heavy metal control at an abandoned antimony smelter - Xiao-Hong Ma; Zhuan-Ling Shao; Yu-Han Wang; Wei-Di Tu; Li-Bang Ma; Jiao Wang (Environmental Geochemistry and Health, 2025)

Machine Learning-Assisted Diagnosis of Abrupt Air Pollution Emissions: Insights From Firework Emissions in China - Lu Yang; Di Liu; Han Yang; Jie Fang; Qingxiao Meng; Yunjiang Zhang; Xinlei Ge (Aerosol Science and Engineering, 2025)

A site experiment on the effects of cool coating in a residential community under the tropical climate - Yong Ping Long; E. V. S. Kiran Kumar Donthu; Di Han; Man Di Zhou; Xiao Qin Zhang; Bing Feng Ng; Man Pun Wan (Sustainable Cities and Society, 2025)

Magnetic effervescence-assisted salting-out liquid-liquid extraction enables fast and effortless determination of pyrethroid insecticide residues in fresh fruits and herbal plants - Zhifei Fu; Xinyue Wang; Jinqing You; Wenxuan Li; Lifeng Han; Liming Wang; Di Chen (Food Chemistry, 2025)

Indication of triple oxygen isotopes to replenishment mechanisms and evaporation processes in Yongding River Basin, North China - Yaxin Zhu; Guilin Han; Di Wang; Shitong Zhang; Xi Gao (Applied Geochemistry, 2025)

Precise identification of faults research based on expanding frequency seismic data - Si Guo; Hai-Sang Ban; Tian-Wen Hu; Chong Han; Yu Peng; Di Zhao; Zong-Wei Wu (Applied Geophysics, 2025)

FCV activates NLRP3 inflammasome through ion-dependent pathway to promote IL-1β secretion - Hongtao Chen; Shihui Zhao; Shanling Liu; Yiming Wei; Yanbing Guo; Kun Gao; Hongze Shao; Han Zhao; Di Bao; Shuang Zhang; Shushuai Yi; Kai Wang; et al. (Veterinary Microbiology, 2025)

Ecological risk-based soil thresholds for polycyclic aromatic hydrocarbons (PAHs) addressing direct contact and food chain exposure in China - Guoxiang Han; Yuchuan Huang; Meirong Yang; Dongyue Meng; Hongmei Xia; Haotian Cui; Di Du (Science of The Total Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Biaxially oriented polyethylene (BOPE) and exogenous H2S extend strawberry shelf-life by increasing antioxidant activity and inhibiting pigment accumulation - Ying-Chun Song; Yu-Qi Zhao; Chi-Ming Tang; Pedro Garcia-Caparros; Si-Yu Yang; Jia-Qi Yu; Xiu-Ting Hu; Kang-Di Hu; Zhuo Han; Hua Zhang; Gai-Fang Yao (Postharvest Biology and Technology, 2025)

Improved antifouling and regeneration capability of polyaniline-modified halloysite nanotube/MXene composite membranes - Jing-Yi Feng; Wen-Hao Geng; Ru-Yu Chang; Yu-Han Wang; Yue-Xin Wang; Ze-Long Bao; Wen-Yi Sun; Lu-Yao Tian; Di Zhang; Hong-Zhang Geng (Journal of Water Process Engineering, 2025)

Enhanced sulfamethoxazole (SMX) degradation by Shewanella oneidensis MR-1 via a microbially driven Fenton reaction - Qing-Jiahui Fan; Wei Li; Gen-Ji Yao; Zu-Hao Wang; Han Fu; Yong-Di Liu; Bruce E. Rittmann (Journal of Water Process Engineering, 2025)

Effects of Microplastic on Rice Seed Germination Mitigated by Brassinolide - Momo Gui; Di Wu; Lijun Han; Hongji Pan; Ming Zhuang; Shiyu Wang; Mengyuan Cao; Jin Hua (Bulletin of Environmental Contamination and Toxicology, 2025)

Valorizing copper-contaminated manure into biochar for tetracycline adsorption: Dynamics and interactions of tetracycline adsorption and copper leaching - Haoxiang Xiong; Xiaojing Zhao; Kai Song; Di Gao; Zengling Yang; Lujia Han (Waste Management, 2025)

FoxO4 reduces the damage and mechanism of PEDV-infected IPEC-J2 cells through the NF-κB/MLCK pathway - Yiming Wei; Shihui Zhao; Han Zhao; Di Bao; Jiuyuan Liu; Hongze Shao; Shuang Zhang; Shushuai Yi; Kai Wang; Guixue Hu (Veterinary Microbiology, 2025)

Topological surface states in γ-PtBi2 evidenced by scanning tunneling microscopy - Yunkai Guo; Jingming Yan; Wen-Han Dong; Yongkai Li; Yucong Peng; Xuetao Di; Caizhen Li; Zhiwei Wang; Yong Xu; Peizhe Tang; Yugui Yao; Wenhui Duan; et al. (Science Bulletin, 2025)

Superior water disinfection via ozone micro-bubble aeration: Performance and mechanism - Zi-Chen Yang; Lu Peng; Zi-Bo Jing; Wen-Long Wang; Han-Ying Cai; Yi-Qing Jiang; Long-Di Li; Bei Ye; Qian-Yuan Wu (Journal of Hazardous Materials, 2025)

Construction of a quadra-functional MXene-mediated photocatalytic solar-driven interfacial evaporation materials: The regulation strategy of MXene in enhancing seawater evaporation and degradation - Yiying Yue; Yun Bai; Di Wang; Wanli Cheng; Qinglin Wu; Guangping Han; Jianchun Jiang (Desalination, 2025)

Conductive polypyrrole-coated ion-sieve composite membrane with rapid and high-capacity lithium-ion adsorption under an electric field for lithium extraction and recovery - Zheng Li; Xiaolong Ding; Yue Zhu; Yingzhe Zhao; Meijun Liu; Shuyu Han; Di Gao; Song Wang (Chemical Engineering Journal, 2025)

Bioinspired copper-doped covalent organic polymers with laccase-mimicking activity for on-site monitoring of thiram in fruit and vegetable samples - Ya Di Shi; Meng Ping Wang; Han Wu; Sai Jin Xiao; Zi Yang Yue; Ding Zhong Yuan; Xin Xin Shao; Feng Tao Yu; Li Zhang (Analytica Chimica Acta, 2025)

Low-coverage whole-genome sequencing for differentiating cervical cancer from cervical intraepithelial neoplasia and benign diseases - Tingting Zhang; Fang Gu; Jia yi He; Weihua Li; Ruxue Han; Xinyu Liu; Chan Dai; Zhendong Qin; Di Zhang; Jun Lu; Hua Li (Chromosome Research, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Lobopaucinoids A-Q, bioactive terpenoids from the soft coral Lobophytum pauciflorum collected in the South China Sea - Xiao Han; Di Zhang; Xiaolei Li; Xiaobin Li; Xuli Tang; Guoqiang Li (Phytochemistry, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Effects of co-fermentation with different erythritol producing abilities Yarrowia lipolytica on the flavor, functionality, and sensory characteristics of Huangjiu - Shen Li; Yijin Yang; Yongjun Xia; Li Ni; Di Han; Lianzhong Ai (Food Research International, 2025)

Butterfly-inspired structures on strong and tough metagel for enhanced passive radiative and evaporative cooling - Di Han; Jipeng Fei; Yongping Long; Yuanhang Yang; Anna Lushnikova; Hiba Mhiri; Christophe Ménézo; Man Pun Wan; Hong Li; Xuan Zhang; Bing Feng Ng (Chemical Engineering Journal, 2025)

Co-combustion reaction of corn stalk hydrochar and anthracite: Kinetics, mechanism and CO2 emission reduction - Wang Liang; Yihao Cui; Di Zhu; Yihan Chen; Yonghui Han; Lin Yue; Chunhe Jiang; Runsheng Xu; Xiaojun Ning; Jianliang Zhang; Chuan Wang; Guangwei Wang (Fuel, 2025)

Phase control of MoWS2 nanostructures via oxalic acid-assisted electron injection: From molybdenum disulfide to tungsten disulfide - Xiao-Yu Chen; Yuan Zhao; Zi-Han Liu; Yi-Tong Pang; Di-Gen Wei; Jing-Yi Wangchen; Cheng-Bao Yao (Chemical Engineering Journal, 2025)

Constructing MO/TMDs heterostructures: Photoelectrochemical activity and charge transfer mechanism investigation - Zi-Han Liu; Xiao-Yu Chen; Yuan Zhao; Yi-Tong Pang; Di-Gen Wei; Jing-Yi Wangchen; Cheng-Bao Yao (Chemical Engineering Journal, 2025)

Exploring the role of dipole moment at the upper interface of inverted perovskite solar cells through a bi-molecular host–guest strategy - Guoqiang Xu; Imran Muhammad; Danish Khan; Xiaojian Zheng; Yu Zhang; Min Xin; Huaxi Gao; Jiahao Li; Junyu Wang; Di Lu; Shehzad Ahmed; Peng You; et al. (Chemical Engineering Journal, 2025)

Xifeng Jiannao pill mitigates MPTP-induced neuronal apoptosis by reducing inflammation and oxidative stress via MAPK signaling - Xiangli Han; Guoping He; Juanjuan Wang; Hanxi Lou; Lei Chen; Lei Zhang; Boyang Liu; Di Wu; Xiaozhi Liu; Su Wang; Chunyan Zhang; Liping Guo (Metabolic Brain Disease, 2025)

Deciphering unique enzymatic pathways in sulfonamide biotransformation by direct ammonia oxidizer Alcaligenes ammonioxydans HO-1 - Jia-Xin Zhang; Ting-Ting Wei; Di Min; Jun-Lu Lv; Dong-Feng Liu; Jie-Jie Chen; Yang-Yang Yu; Han-Qing Yu (Water Research, 2025)

Ultrasound-assisted deep eutectic solvent extraction of kukoamine A and kukoamine B from Lycii cortex - Xiaomei Wang; Jinxia Hu; Ling Ma; Zhiming Han; Jianfei Liu; Zhibin Lu; Dong Pei; Ningli Wang; Duolong Di (Phytochemistry Letters, 2025)

Large-scale genomic and phenomic analyses of modern cultivars empower future rice breeding design - Xiaoding Ma; Hao Wang; Shen Yan; Chuanqing Zhou; Kunneng Zhou; Qiang Zhang; Maomao Li; Yaolong Yang; Danting Li; Peng Song; Cuifeng Tang; Leiyue Geng; et al. (Molecular Plant, 2025)

Lactiplantibacillus plantarum T34 alleviates constipation by enhancing intestinal barrier and modulating gut homeostasis - Fei Shen; Huiting Zhu; Zhongyan Bao; Di Han; Juan Du; Minjie Zhao; Fengqin Feng; Guanghua He; Qiufen Mo (Food Bioscience, 2025)

New insights into the Fe(III)-activated peroxyacetic acid: Oxidation properties and mechanism - Songyun Liu; Fei Di; Zhan Lian; Guang Wang; Qi Yu; Donghui Han (Environmental Research, 2025)

Dry-processing of VN quantum dots/N, O, S-doped hierarchical porous carbon electrodes with high sulfur-loading for practical lithium-sulfur batteries - Shixian Chen; Gaohui Du; Yan Cheng; Di Han; Jiahao Deng; Yunting Wang; Huayu Li; Libing Yao; Dong Wang; Qingmei Su; Bingshe Xu (Chemical Engineering Journal, 2025)

Indole alkaloids from endophytic fungus Robillarda sessilis and their antibacterial activity - Zediao Huang; Di Wu; Xueqiong Liu; Qingpei Liu; Xiaole Han; Wenjing Wang; Xiaolong Yang (Natural Product Research, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Transcriptome profiling in peanut (Arachis hypogaea) in response to biotic stress produce by Bacillus amyloliquefaciens TA-1 - Wang Chen; Taswar Ahsan; Di Han; Wen-Rui Wang; Si-Tong Du; Chao-Qun Zang; Yu-Qian Huang; Ejaz Hussain Siddiqi (Plant Gene, 2025)

Evaluation of the detoxification effect and toxicity mechanism of Fenton process for pulping wastewater treatment - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Yan Wang (Journal of Water Process Engineering, 2025)

Fabrication and characterization of lysozyme fibrils/Zein complexes for resveratrol encapsulation: Improving stability, antioxidant and antibacterial activities - Min Huang; Yuling Song; Han Wang; Hao Li; Rongmi Zhou; Qing Cao; Lijuan Dong; Gerui Ren; Di Wu; Qunfang Lei; Wenjun Fang; Dan Deng; et al. (Food Chemistry, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

Electrostatic repellent dispersion method for green and cost-effective aqueous radiative cooling paint - Jipeng Fei; Di Han; Kai Zhou; See Wee Koh; Junyu Ge; Jun Yan Tan; Bing Feng Ng; Zhong Chen; Lili Cai; Hong Li (Building and Environment, 2025)

Correction: Colonization of Serendipita indica enhances resistance against Phoma arachidicola in Arachis hypogaea L - Chen Wang; Taswar Ahsan; Ao Ding; Di Han; Jie Gao; Chun-Hao Liang; Si-Tong Du; Yi Wei; Yu-Qian Huang; Shi-Hong Zhang (World Journal of Microbiology and Biotechnology, 2025)

Colonization of Serendipita indica enhances resistance against Phoma arachidicola in Arachis hypogaea L - Chen Wang; Taswar Ahsan; Ao Ding; Di Han; Jie Gao; Chun-Hao Liang; Si-Tong Du; Yi Wei; Yu-Qian Huang; Shi-Hong Zhang (World Journal of Microbiology and Biotechnology, 2025)

Genome-wide association study to identify candidate genes for submergence tolerance during rice seed germination - Qiuyu Zhang; Bing Han; Di Cui; Zhengwu Zhao; Longzhi Han; Xiaoding Ma (Theoretical and Applied Genetics, 2025)

Rosiglitazone Promotes Oligodendrocyte Development and Myelin Formation of Repeated Neonatal Sevoflurane Exposure via PPARγ Signaling - Tianyu Cao; Sufang Jiang; Xueji Wang; Peiying Huang; Lijie Zhou; Lichao Di; Shuang Han; Lining Huang (Molecular Neurobiology, 2025)

Vocal differences in note, sequence and great call sequence among three closely related Nomascus gibbon species - Pu Han; Hai-gang Ma; Zi-di Wang; Peng-lai Fan; Peng-fei Fan (International Journal of Primatology, 2025)
The vocal structure of gibbons has long been believed to be under strong genetic control and consistent with phylogeny. Gibbon vocalizations show hierarchical structures and song coordination behaviors, which may have different functions and convey distinct information compared to basic notes. However, previous studies have not compared vocalizations at multiple levels across species. We compared the vocal structures of three Nomascus species in the wild in South China, namely the western black gibbon ( Nomascus concolor ), Cao vit gibbon ( N. nasutus ), and Hainan gibbon ( N. hainanus ) at the levels of note (six features of four types of notes), male sequence (eight features), and song coordination (four features of the overlap pattern between male and female songs). We selected 15 recordings for each species: N. concolor (six groups, 2006 to 2021), N. nasutus (seven groups, 2008 to 2021), and N. hainanus (six groups, 2020 to 2021). We used permuted random forest analysis to test for species differences in vocal structure and the contribution of acoustic features to species differences at each level. We used acoustic features to construct a hierarchical clustering tree, and compared it with phylogenetic relationships. We found significant differences at all levels except the boom note. Acoustic similarity did not match genetic similarity in boom and pre-modulated notes, suggesting that genetic differences are not the only factor leading to species differences in vocal structures. We also found different contributions of acoustic features to differentiation in vocal structure at different levels. Our study suggests that we need to compare gibbon vocalizations at different levels to understand their differentiation and evolution.

Enhanced wastewater treatment using biochar-supported layered-double-hydroxide composites - Ao Huang; Nan Zhang; Qian-Bin Wang; Bo-Han Zhao; Rui-Bao Zhang; Ming Cheng; Chen Shi; Xiao-Di Hao (Chemical Engineering Journal, 2025)

An eco-friendly kapok fiber-supported liquid microextraction using natural deep eutectic solvent as extractant for convenient biological samples preparations: A proof-of-concept study - Wen-Chao Han; Xin-Ying Wang; Gao-Biao Wang; Han-Juan Zhang; Pei Yang; Jin-Chao Wei; Yu-Ling Yang; Dong-Dong Yuan; Di Chen (Sustainable Chemistry and Pharmacy, 2024)

Simulating the multi-media fate of perfluorooctane sulfonate (PFOS) and its precursors in the Bohai coastal region of China - Guoxiang Han; Shuai Song; Di Du; Haotian Cui; Yonglong Lu; Rui Wang (Science of The Total Environment, 2024)

Organic fertilizer significantly mitigates N2O emissions while increase contributed of comammox Nitrospira in paddy soils - Han Sun; Youfa Li; Yating Xing; Dylan Bodington; Xing Huang; Chenxiao Ding; Tida Ge; Hongjie Di; Jianming Xu; Cécile Gubry-Rangin; Yong Li (Science of The Total Environment, 2024)

Response of aerobic granular sludge to salinity fluctuations in formation, stability and microbial community structures - Jie Xu; Shichang Liu; Jiazhong Zhou; Lin Li; Xuejun Bi; Wenjie Han; Di Wu (Science of The Total Environment, 2024)

Unmanned vehicles probed inner-core air-sea conditions during Super Typhoon Koinu (2023) - Han Zhang; Di Tian; Yutong Sun; Ming Yang; Shaoqiong Yang; Ying Zhou; Xiujun Sun; Dake Chen (Science Bulletin, 2024)

Enhanced biochemical treatment of pulping wastewater by Fenton process: Water quality optimization and detoxification efficiency - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Yan Wang (Journal of Environmental Chemical Engineering, 2024)

Scheelite as a microtextural and geochemical tracer of multistage ore-forming processes in skarn mineralization: A case study from the giant Xintianling W deposit, South China - Hongfei Di; Yong-Jun Shao; Yi-Qu Xiong; Han Zheng; Xiang Fang; Wenjie Fang (Gondwana Research, 2024)

Shell engineering afforded dielectric polarization prevails and impedance amelioration toward electromagnetic wave absorption enhancement in nested‐network carbon architecture - Lixue Gai; Honghong Zhao; Xueai Li; Pan Wang; Shuping Yu; Yongzheng Chen; Chunsheng Wang; Di Lan; Fei Han; Yunchen Du (Chemical Engineering Journal, 2024)

Interaction of biochar with extracellular polymers of resistant bacteria restrains Pb(II) adsorption onto their composite: Macro and micro scale investigations - Di Wang; Hansong Chen; Hui Han; Wenwen Yang; Qi Sun; Churong Cao; Kai Ning; Zhuochun Huang; Ting Wu (Bioresource Technology, 2024)

Circular RNA and its potential diagnostic and therapeutic values in breast cancer - Di Gao; Can Cui; Yaoxuan Jiao; Han Zhang; Min Li; Junjie Wang; Xiumei Sheng (Molecular Biology Reports, 2024)

Correction to: Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; Jonas De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Protective effects of polysaccharide from Atractylodes macrocephala Koidze (PAMK) as a feed additive on growth performance, immunity, antioxidant capacity, and disease resistance against Aeromonas salmonicida in rainbow trout (Oncorhynchus mykiss) - Shaoxia Lu; Xunwen Bian; Chang’an Wang; Di Wang; Honghe Shi; Shidi Wang; Gefeng Xu; Hongbai Liu; Shicheng Han (Aquaculture International, 2024)

Near-inertial ocean response to a typhoon on a continental slope in the Northern South China Sea - Han Zhang; Renhao Wu; Fu Liu; Xiaobo Ni; Di Tian (Frontiers in Marine Science, 2024)
Typhoons are strong natural events that significantly influence the marine environment. In 2018, Typhoon Mangkhut traveled over a moored station with a depth ~1900 m on continental slope in the northern South China Sea, the near-inertial oceanic responses are studied based on the Regional Ocean Modeling System (ROMS) model simulation combined with observation data. Near-inertial currents after Mangkhut can be divided into three layers: near-circular polarized in upper ocean, across-slope polarized in deep ocean and along-slope polarized near the bottom, thickness of the three layers depend on the slope steepness. According to across-slope and along-slope intensified currents, the near-bottom vertical velocities and near-inertial energy were intensified at the moored station. The across-slope forth/back near-inertial flows brought cold/warm and salty/fresh water from deeper/shallower depth, increased vertical excursions of near-bottom temperature/salinity isolines and near-inertial available potential energy. The near-inertial barotropic across-slope currents were much greater than along-slope currents, with net cooling and salinity increase of the whole water column at the moored station. The core responses to Mangkhut were within 100 km around the station. The near-inertial kinetic energy generated both at sea surface and bottom slope, then propagated vertically into ocean interior and horizontally into the South China Sea basin as well as some topography-trapped waves propagated along the slope. This work enriches the understanding of air–sea interactions in coastal regions and the effect of ocean topography, especially after a typhoon.

Oceanic response to tropical cyclone in the northern South China Sea observed by underwater gliders during 2018 and 2020 - Yanfeng Zhang; Han Zhang; Xiaodong Tang; Shaoqiong Yang; Yanhui Wang; Xiayan Lin; Di Tian; Dake Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Replacing sea mud with attachment of suspension cage can improve growth and gut health for sea cucumber Apostichopus japonicus - Zhixu Guo; Xiangyu Meng; Yuntian Zhang; Di Wu; Rongwei Zhang; Xiaoran Zhao; Tongjun Ren; Yuzhe Han (Frontiers in Marine Science, 2024)
During the suspension cage culture procedure, a substantial quantity of attachments from the suspension cage will amass in the tidal flats, resulting in environmental pollution and resource wastage. The aim of the present study was to explore the feasibility of using attachments of suspension cage (ASC) as a raw feed material for sea cucumbers. Different ASC concentrations (0, 25, 50, 75, and 100%) were used in sea cucumber ( Apostichopus japonicus ) fed for 60 d. Replacing sea mud with 50% ASC significantly improved sea cucumber growth, reduced the feed coefficient, significantly increased the activity of intestinal digestive enzymes, improved the activities of acid phosphatase and alkaline phosphatase, improved the intestinal structure, and enriched intestinal microbiome diversity ( P <0.05). Replacing sea mud with 75% and 100% ASC significantly improved sea cucumber total antioxidant capacity and total superoxide dismutase ( P <0.05).Furthermore, expressions of c-myc gene, mapk-7 gene and fgfr-1 gene, which all three growth genes, significantly increased in the 50% ASC treatment compared to that in the control; whereas, that of gdf-8 gene, a negative growth regulator, was inhibited ( P <0.05). Based on the quadratic regression analysis for the weight gain rate, the appropriate levels of ASC substitution were estimated as to be 44.28%. The results suggested the potential of ASC as a new raw feed material for sea cucumbers.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular characterization of petroleum acids from diverse geological origins via n-Butylsilane reduction - Haojie Hu; Shuofan Li; Yuanfeng Wang; Ruochen Yang; Jianxun Wu; Weilai Zhang; Chen He; Han Li; Yahe Zhang; Di Zhu; Quan Shi (Fuel, 2024)

Distribution characteristics of sulfonamide antibiotics between water and extracellular polymeric substances in municipal sludge - Ming Cheng; Chen Shi; Bo-Han Zhao; Tai-Yue Wang; Nan-Zhang; Ran-Bin Liu; Da-Qi Cao; Xiao-Di Hao (Environmental Research, 2024)

Deep learning model for precise prediction and design of low-melting point phthalonitrile monomers - Rongxing Lu; Yue Han; Junbao Hu; Di Xu; Zhixuan Zhong; Heng Zhou; Tong Zhao; Jian Jiang (Chemical Engineering Journal, 2024)

Pyrene-4,5,9,10-tetraone-based covalent organic framework/carbon nanotube composite as sodium-ion cathodes with high-rate capability - Lei Chen; Yuke Li; Yuemiao Zhang; Shi-Bin Ren; Jinhai Bi; Xinxian Xue; De-Man Han; Di Wu; Yujing Wang; Xianlang Chen; Yingpeng Wu (Chemical Engineering Journal, 2024)

A sulfhydryl-functionalized vinylene-linked covalent organic framework for promoting gold recovery by light-assistance - Di Jiang; Zhen-Lei Wang; Yuan-Zhe Cheng; Ya-Xi Yu; Hui-Yuan Kong; Xin-Yue Bian; Xiao-Meng Dou; Shun-Li Li; Dong-Hui Yang; Xuesong Ding; Bao-Hang Han (Chemical Engineering Journal, 2024)

Spatial relevance of synergistic effects between air pollutants and carbon dioxide emission reductions: A case study in the Bohai Rim region of China - Nan Han; Di Li; Zenglin Han; Hongye Wang; Ye Duan (Atmospheric Pollution Research, 2024)

Harnessing the power of tidal flat diatoms to combat climate change - Jihae Park; Hojun Lee; Jana Asselman; Colin Janssen; Stephen Depuydt; Jonas De Saeger; Thomas Friedl; Koen Sabbe; Wim Vyverman; Catharina J. M. Philippart; Jaime Pitarch; Philippe M. Heynderickx; et al. (Critical Reviews in Environmental Science and Technology, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Downregulated Expression and Hypermethylation of SIRT1 in Patients with Kashin-Beck Disease–Mediated Chondrocyte Apoptosis May Potentially Be Ameliorated by Selenium Supplement - Xiaoli Yang; Lixin Han; Di Zhang; Cuixiang Xu; Zhankui Jin; Yongmin Xiong (Biological Trace Element Research, 2024)

Effects of melatonin on sperm quality, enzyme activity, antioxidant gene expression and fertility of cryopreserved bovine semen - Peng Niu; Fei Huang; Jie Wang; Jia-jia Suo; Jie-ru Wang; Di Fang; Chun-mei Han; Qing-hua Gao (Theriogenology, 2024)

Transitioning weathered oil fields towards new energy: A review on utilizing hydrogenotrophic methanogens for petroleum hydrocarbons remediation - Jiaping Zhou; Wei-Han Lin; Ying-Liang Yu; Cheng-Di Dong; Haibing Zhang; Zhongtao Hu; Chih-Ming Kao (Journal of Hazardous Materials, 2024)

A multi-omics-based investigation into the regulation of phenolics in fresh maize kernels at different developmental stages - Xiaomin Tian; Di Han; Linlin Sun; Yuqiu Guo; Kaichang Liu; Lirong Chen; Kuijie Gong (Journal of Cereal Science, 2024)

3D macroporous MXene/sodium alginate aerogels with “brick-concrete” structures for highly efficient solar-driven water purification - Yang Zhang; Shuai Wang; Di Han; Hongxuan Chen; Huiquan Liu; Jie Zhu; Wen Luo; Changrui Shi; Yongchen Song; Zheng Ling (Desalination, 2024)

Global quantitative synthesis on the patterns and drivers of funneling ratio and enrichment ratio for stemflow - Meng-Di Wu; Zhi-Yun Jiang; Xiao Yang; Buerlan Yeerbolati; Lin Huang; Ying-Yin Zhong; Han-Wen Zhang; Xiao-Yan Li (CATENA, 2024)

Prenylated dihydroflavones from the root barks of Morus alba - Jun-Yu Zhu; Han-Zhuang Weng; Di-Kai Tang; Jin-Chen Long; Zhuo-Ya Tang; Ye Chen; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

The BLV-miRNAs pathway of BLV inhibits the expression of Lactoferrin, Lactoperoxidase, Alpha-lactalbumin and Beta-lactoglobulin proteins - Shuai Lian; Han Zhang; Yandi Wang; Jiahe Song; Pengfei Liu; Zijian Geng; Rui Wu; Di Wang; Jianfa Wang (Veterinary Microbiology, 2024)

Modelling dynamic fracture and fragmentation of rocks under multiaxial coupled static and dynamic loads with a parallelised 3D FDEM - Haoyu Han; Daisuke Fukuda; Hongyuan Liu; Qianbing Zhang; Jian Zhao; Di Wu; Andrew Chan (Computers and Geotechnics, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

A competitive strategy toward 1 T/2H MoS2 to balance impedance for optimizing electromagnetic wave absorption - Qilin Jiang; Lei Xu; Zhimeng Tang; Cheng Xie; Junyu Lu; Zhaohui Han; Di Zhang; Changhao Zuo (Chemical Engineering Journal, 2024)

Heterologous expression of P9 from Akkermansia muciniphila increases the GLP-1 secretion of intestinal L cells - Wenxuan Di; Yuchen Zhang; Xinyuan Zhang; Luxuan Han; Liang Zhao; Yanling Hao; Zhengyuan Zhai (World Journal of Microbiology and Biotechnology, 2024)

Anthropogenic gadolinium sources and remediation in highly urbanized river in the Beijing-Tianjin-Hebei (BTH) region, China: Insights from buffer zone and three-dimensional tracer system - Xi Gao; Guilin Han; Shitong Zhang; Jinke Liu; Di Wang; Shunrong Ma; Yuqing Zhao (Process Safety and Environmental Protection, 2024)

Sustainability information, taste perception and willingness to pay: The case of bird-friendly coffee - Klaus G. Grunert; Han-Seok Seo; Di Fang; Victoria J. Hogan; Rodolfo M. Nayga Jr. (Food Quality and Preference, 2024)

The effect of fracture aperture and matrix permeability on suitability of the equivalent porous medium model for steady-state flow in fractured porous media - Di Han; Lei Ma; Jiazhong Qian; Di Gao; Haichun Ma; Qiankun Luo; Pengyu Qiu (Hydrogeology Journal, 2024)

Effective method for identification of preferential flow paths in two-dimensional discrete fracture networks based on a flow resistance method - Lei Ma; Xuelin Cui; Chunchao Zhang; Jiazhong Qian; Di Han; Yongshuai Yan (Hydrogeology Journal, 2024)

Quantitative Applications of Weather Satellite Data for Nowcasting: Progress and Challenges - Jun Li; Jing Zheng; Bo Li; Min Min; Yanan Liu; Chian-Yi Liu; Zhenglong Li; W. Paul Menzel; Timothy J. Schmit; John L. Cintineo; Scott Lindstrom; Scott Bachmeier; et al. (Journal of Meteorological Research, 2024)

The effects and mechanisms of deep straw incorporation and denitrifying bacterial agents on mitigating nitrate leaching and N2O emissions in four soil types in the North China Plain - Ya-Bo Zhang; Si-Yi Liu; Jun-Tao Wang; Hong J. Di; Li-Li Han; Pei-Pei Li; Ju-Pei Shen; Bing Han; Li-Mei Zhang (Agriculture, Ecosystems & Environment, 2024)

Crosstalk among proximal tubular cells, macrophages, and fibroblasts in acute kidney injury: single-cell profiling from the perspective of ferroptosis - Yulin Wang; Ziyan Shen; Shaocong Mo; Han Zhang; Jing Chen; Cheng Zhu; Shiqi Lv; Di Zhang; Xinhui Huang; Yulu Gu; Xixi Yu; Xiaoqiang Ding; et al. (Human Cell, 2024)
The link between ferroptosis, a form of cell death mediated by iron and acute kidney injury (AKI) is recently gaining widespread attention. However, the mechanism of the crosstalk between cells in the pathogenesis and progression of acute kidney injury remains unexplored. In our research, we performed a non-negative matrix decomposition (NMF) algorithm on acute kidney injury single-cell RNA sequencing data based specifically focusing in ferroptosis-associated genes. Through a combination with pseudo-time analysis, cell–cell interaction analysis and SCENIC analysis, we discovered that proximal tubular cells, macrophages, and fibroblasts all showed associations with ferroptosis in different pathways and at various time. This involvement influenced cellular functions, enhancing cellular communication and activating multiple transcription factors. In addition, analyzing bulk expression profiles and marker genes of newly defined ferroptosis subtypes of cells, we have identified crucial cell subtypes, including Egr1 + PTC-C1, Jun + PTC-C3, Cxcl2 + Mac-C1 and Egr1 + Fib-C1. All these subtypes which were found in AKI mice kidneys and played significantly distinct roles from those of normal mice. Moreover, we verified the differential expression of Egr1, Jun, and Cxcl2 in the IRI mouse model and acute kidney injury human samples. Finally, our research presented a novel analysis of the crosstalk of proximal tubular cells, macrophages and fibroblasts in acute kidney injury targeting ferroptosis, therefore, contributing to better understanding the acute kidney injury pathogenesis, self-repairment and acute kidney injury-chronic kidney disease (AKI-CKD) progression.

Enhancing Growth and Intestinal Health in Triploid Rainbow Trout Fed a Low-Fish-Meal Diet through Supplementation with Clostridium butyricum - Chang’an Wang; Fangyuan Li; Di Wang; Shaoxia Lu; Shicheng Han; Wei Gu; Haibo Jiang; Zhuang Li; Hongbai Liu (Fishes, 2024)
This study evaluates the effects of dietary Clostridium butyricum on growth performance and intestinal health in triploid rainbow trout (Oncorhynchus mykiss). Administered in a 12-week trial, five isonitrogenous and isolipidic feeds contained different C. butyricum levels [G1 (0), G2 (1.6 × 106 CFU/g), G3 (1.2 × 107 CFU/g), G4 (1.1 × 108 CFU/g), and G5 (1.3 × 109 CFU/g)]. Significant enhancements in growth performance, including improved feed conversion ratios and specific growth rates in the G4 group, were indicative of enhanced nutrient utilization, corroborated by optimal digestive enzyme activity levels. Antioxidant capabilities were also enhanced in the G4 group, indicated by increased serum superoxide dismutase and catalase activities, along with a significant decrease in malondialdehyde levels. Gut microbiota analysis indicated a probiotic concentration-dependent modulation of microbial communities, with a marked enrichment in beneficial bacterial phyla like Firmicutes in the G4 group. This microbial shift correlated with significant downregulations in immune-related gene expressions, including interleukins (IL-1β, IL-8), NF-κB, MyD88, and TNF-α, highlighting an activated immune response. Correspondingly, serum lysozyme and immunoglobulin M contents were significantly elevated in the G4 group. Challenge tests with Aeromonas salmonicida exhibited the higher disease resistance of fish fed the G4 diet. In conclusion, the study shows the potential of dietary C. butyricum, especially at 1.1 × 108 CFU/g, in enhancing the growth, health, and disease resistance of triploid rainbow trout through modulating gut microflora and stimulating immune responses.

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Determining hydrogen and oxygen isotopes to reflect the responses of rainfall process on urban activities: Insight from the extreme rainfall period in megacity - Yaxin Zhu; Guilin Han; Jie Zeng; Di Wang (Urban Climate, 2024)

Rice straw returning enhances cadmium activation by accelerating iron cycling thus hydroxyl radical production in paddy soils during drainage - Hui Huang; Zhuoqi Tian; Di Guo; Zhixian Tang; Ronghua Li; Amjad Ali; Zhengxian Cao; Haiying Lu; Yu Shen; Yongli Zhu; Jiangang Han (Science of The Total Environment, 2024)

Generation of CRISPR-edited birch plants without DNA integration using Agrobacterium-mediated transformation technology - Shilin Sun; Xue Han; Ruoxuan Jin; Junbo Jiao; Jingwen Wang; Siyuan Niu; Ziyao Yang; Di Wu; Yucheng Wang (Plant Science, 2024)

Multi-dimensional low-carbon assessments of wind-driven seawater desalination system via hybrid life cycle modeling - Siyuan Liu; Di Song; Mengyao Han; Chao Ai; Quan Shan; Zihan Liu; Gengxin Zhang (Environmental Impact Assessment Review, 2024)

Secreted Glycoproteins That Regulate Synaptic Function: the Dispatchers in the Central Nervous System - Haiying Gong; Conglei Zhu; Di Han; Sen Liu (Molecular Neurobiology, 2024)

Characteristics of bacterial community structure in the sediment of Chishui River (China) and the response to environmental factors - Fei Di; Donghui Han; Guang Wang; Wenbo Zhao; Daokun Zhou; Nan Rong; Shou Yang (Journal of Contaminant Hydrology, 2024)

Usefulness of techniques to measure and model crop growth and yield at different spatial scales - Di He; Enli Wang; John Kirkegaard; Eusun Han; Brendan Malone; Tony Swan; Stuart Brown; Mark Glover; Roger Lawes; Julianne Lilley (Field Crops Research, 2024)

High-Performance low-k Poly(dicyclopentadiene)-POSS nanocomposites achieved by frontal polymerization - Dai-Lin Zhou; Jian Wang; Hongwei Bai; Di Han; Qiang Fu (Chemical Engineering Journal, 2024)

Computational Comparison of the Mechanical Behavior of Aortic Stent-Grafts Derived from Auxetic Unit Cells - Rahul Vellaparambil; Woo-Suck Han; Pierluigi Di Giovanni; Stéphane Avril (Cardiovascular Engineering and Technology, 2024)
Purpose Inappropriate stent-graft (SG) flexibility has been frequently associated with endovascular aortic repair (EVAR) complications such as endoleaks, kinks, and SG migration, especially in tortuous arteries. Stents derived from auxetic unit cells have shown some potential to address these issues as they offer an optimum trade-off between radial stiffness and bending flexibility. Methods In this study, we utilized an established finite element (FE)-based approach to replicate the mechanical response of a SG iliac limb derived from auxetic unit cells in a virtual tortuous iliac aneurysm using a combination of a 180° U-bend and intraluminal pressurization. This study aimed to compare the mechanical performance (flexibility and durability) of SG limbs derived from auxetic unit cells and two commercial SG limbs (Z-stented SG and circular-stented SG models) in a virtual tortuous iliac aneurysm. Maximal graft strain and maximum stress in stents were employed as criteria to estimate the durability of SGs, whereas the maximal luminal reduction rate and the bending stiffness were used to assess the flexibility of the SGs. Results SG limbs derived from auxetic unit cells demonstrated low luminal reduction (range 4–12%) with no kink, in contrast to Z-stented SG, which had a kink in its central area alongside a high luminal reduction (44%). Conclusions SG limbs derived from auxetic unit cells show great promise for EVAR applications even at high angulations such as 180°, with acceptable levels of durability and flexibility.

Shaking table test study on performance and functionality of a typical telecommunication room after earthquakes - Bo Li; Endong Guo; Guoliang Sun; Shuqiang Ji; Chenxi Mao; Tao Wang; Di Han; Xiaofei Li (Earthquake Engineering and Engineering Vibration, 2024)

A new combined atmospheric correction algorithm for GOCI-2 Data over coastal waters assessed by long-term satellite ocean color platforms - Feng Qiao; Jianyu Chen; Bing Han; Qingjun Song; Qiankun Zhu; Di Jia (International Journal of Remote Sensing, 2024)

Simulating behavior of perfluorooctane sulfonate (PFOS) in the mainstream of a river system with sluice regulations - Guoxiang Han; Shuai Song; Yonglong Lu; Meng Zhang; Di Du; Qiang Wu; Shengjie Yang; Rui Wang; Haotian Cui; Lu Yang; Ruoyu Mao; Bin Sun; et al. (Chemosphere, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

New insights into toxicity reduction and pollutants removal during typical treatment of papermaking wastewater - Fei Di; Donghui Han; Jinquan Wan; Guang Wang; Bin Zhu; Yan Wang; Shou Yang (Science of The Total Environment, 2024)

UV-C radiation promoted flavonoid synthesis during early healing in potato tuber wounds with the possible involvement of ABA and related transcription factor regulation - Xuejiao Zhang; Xiaoyuan Zheng; Ruirui Yang; Qihui Wang; Lu Bai; Di Gong; Ye Han; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2024)

Two heat shock cognate 70 genes involved in spermatogenesis regulate the male fertility of Zeugodacus cucurbitae, as potential targets for pest control - Shan-Yuan Tan; Chuan-Lian Liu; Hong-Liang Han; Xiao-Di Zhai; Hongbo Jiang; Bao-Jun Wang; Jin-Jun Wang; Dong Wei (Pesticide Biochemistry and Physiology, 2024)

Diffusion kinetic processes and release risks of trace metals in plateau lacustrine sediments - Xiang Gu; Xiaotong Han; Peng Xing; Di Xu; Shiqiang Wan; Qinglong L. Wu; Fengchang Wu (Journal of Hazardous Materials, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

Multi-scale failure mechanisms of hydraulic engineering exposed to seasonally frozen salinization environment: Integrating SBAS-InSAR and mechanical experiments - Zhaoxi Wang; Chen Cao; Qingbo Yu; Qing Wang; Cencen Niu; Jiejie Shen; Kuanxing Zhu; Jing Liu; Mengxia Han; Huicheng Fu; Xun Sun; Weitong Xia; et al. (Science of The Total Environment, 2024)

Dynamic Mechanical Responses and Freezing Strengthening Mechanism of Frozen Sandstone with Single Flaw: Insights from Drop Weight Tests and Numerical Simulation - Ke Ma; Fuqiang Ren; Han Wang; Limin Li; Di Wu (Rock Mechanics and Rock Engineering, 2024)

A new capnosane-type diterpenoid from the South China sea soft coral Lobophytum pauciflorum - Di Zhang; Yueying Li; Xiaolei Li; Xiao Han; Zhe Wang; Guoqiang Li (Natural Product Research, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Assessing industrial wastewater effluent toxicity using boosting algorithms in machine learning: A case study on ecotoxicity prediction and control strategy development - Duc-Viet Nguyen; Jihae Park; Hojun Lee; Taejun Han; Di Wu (Environmental Pollution, 2024)

Observed oceanic response to Tropical Cyclone Amphan (2020) from a subsurface mooring in the Bay of Bengal - Yingyu Peng; Di Tian; Feng Zhou; Han Zhang; Xiao Ma; Dingyong Zeng; Qicheng Meng; Beifeng Zhou; Ruijie Ye; Yeqing Chen; Feilong Lin; Zhentao Hu; et al. (Progress in Oceanography, 2023)

Effect of damming on hydrogeochemical characteristics and potential environmental risks in a large reservoir: Insights from different vertical layer sampling - Di Wang; Guilin Han; Mingming Hu; Yuchun Wang; Jinke Liu; Xi Gao (Environmental Research, 2023)

Experimental study of shape memory alloy plates under cyclic tension–compression loading scenarios - Xuhong Zhou; Bin Han; Ke Ke; Jin Di; Fengjiang Qin; Long Hu (Engineering Structures, 2023)

Upper-ocean structure variability in the Northwest Pacific Ocean in response to tropical cyclones - Jie Yu; Han Zhang; Huizan Wang; Di Tian; Jiagen Li (Frontiers in Marine Science, 2023)
The upper ocean structure obviously affects sea surface temperature cooling (SSTC) induced by tropical cyclones (TCs). Herein, principal component analysis of many Argo profiles from 2001 to 2017 in the Northwest Pacific Ocean is used to classify the upper ocean structure. The results suggest that the upper ocean structure can be divided into four types of water. Water with low mode 1 scores (M1-L water) is characterized by an extremely warm sea surface temperature (SST), while a cold and thick isothermal layer is observed for water with high mode 1 scores (M1-H water). Water with high mode 2 scores (M2-H water) has a warm SST and a thick isothermal layer. Relative to M2-H water, water with high mode 3 scores (M3-H water) has a warmer SST but a shallower mixed layer. These waters have remarkable seasonal and spatial variability, mainly associated with the impacts of solar radiation, precipitation, currents and mesoscale eddies. The ocean responses to TCs are different among these water types, which greatly influences the TCs intensification. The response of M1-H water is not considered, since its SST is below 26°C. The TC-induced SSTC of M3-H water (-1.12°C) is markedly higher than that of M1-L (-0.68°C) and M2-H waters (-0.41°C). Moreover, the one-dimensional mixed layer model shows a much smaller entrainment rate for M2-H water due to its thick barrier layer. The number of each water type changes in association with global warming and Kuroshio path, and thus affects the TC intensification.

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Sludge biodrying coupled with photocatalysis improves the degradation of extracellular polymeric substances - Lu Cai; Meng-Ke Cao; Guo-Di Zheng; Xin-Yu Wang; Han-Tong Guo; Tao Jiang (Journal of Environmental Management, 2023)

Large-eddy simulation of dual-fuel spray ignition at varying levels of methane diluted ambient oxidizer using FGM - Hesheng Bao; Jinlin Han; Yan Zhang; Andrea Di Matteo; Dirk Roekaerts; Jeroen Van Oijen; Bart Somers (Fuel, 2023)

Oxidation of Sb(III) by Shewanella species with the assistance of extracellular organic matter - Kai-Li Wang; Di Min; Guan-Lin Chen; Dong-Feng Liu; Han-Qing Yu (Environmental Research, 2023)

Quantifying the late Quaternary incision rate in the upper Jinsha River with dated fluvial terraces and transient tributary profiles - Zhihai Li; Jianping Chen; Zhigang Shan; Yiding Bao; Yuchao Li; Kun Shan; Di Liu; Mengxia Han (CATENA, 2023)

An Intelligent Monitoring System for the Force Characteristics of Floating Bollards in a Ship Lock - Linjian Wu; Jia Yang; Zhouyu Xiang; Mingwei Liu; Minglong Li; Yutao Di; Han Jiang; Chuan Dai; Xudong Ji (Journal of Marine Science and Engineering, 2023)
Due to the large scale of navigation ships, the fast speed of entering the lock, and the irregular mooring and the complicated flow conditions in the lock chamber, it is common for the floating bollards of the lock to suffer structural damage or even failure due to the overloaded mooring force. However, the traditional cable load measurement method cannot offer real-time feedback on force characteristics of floating bollards, making it difficult to accurately judge its service status. To this end, according to the floating bollard structure type and load condition of a representative ship lock project in China, this paper determines the theoretical model parameters of a floating bollard load response based on three-dimensional finite element numerical simulation test data and constructs a modified load response model of floating bollards. On this basis, an intelligent floating bollard monitoring system based on big data, internet, and cloud services is developed to intelligently perceive real-time floating bollard force characteristics and monitor the long-term service status. Relying on a representative ship lock in China, a field test of the floating bollard intelligent monitoring system is carried out. The relative error between the calculated values via the model (i.e., system exhibition results) based on the numerical results and the field-measured values is within 15%. This result verified the accuracy and effect of the monitoring system. This research supports the establishment of the digital perception monitoring platform for ship lock facilities and improves the automation level of ship lock operation and management as well as overall risk prevention and control capabilities.

Preharvest chitooligosaccharide spray alleviates chilling injury in harvested muskmelon fruit by regulating membrane lipid metabolism and activating antioxidant enzyme activity - Zhanhong Han; Baojun Li; Di Gong; Pengdong Xie; Lirong Yu; Yi Wang; Ye Han; Yongcai Li; Dov Prusky; Gianfranco Romanazzi; Yang Bi (Postharvest Biology and Technology, 2023)

Incorporating a new landscape intensity indicator into landscape metrics to better understand controls of water quality and optimal width of riparian buffer zone - Haojie Han; Xing Yan; Haiwen Xie; Jie Qiu; Xianghua Li; Di Zhao; Xiaohan Li; Xiaoyuan Yan; Yongqiu Xia (Journal of Hydrology, 2023)

Self-healing polyurethane coatings based on dynamic chemical bond synergy under conditions of photothermal response - Kang Chen; Haoxin Zhu; Zhiyi Zhang; Yingqing Shao; Qianhui Yu; Xinlei Cao; Siyan Pan; Xin Mu; Zhenhua Gao; Di Wang; Shuangying Wei; Shuaiyuan Han (Chemical Engineering Journal, 2023)

A new algorithm for real-time detection of window opening area in residential buildings - Yiqiao Liu; Wen Tong Chong; Yat Huang Yau; Di Han; Mingyuan Qin; Fei Deng; Xiyao Wang; Song Pan (Building and Environment, 2023)

cPKCγ-Modulated Autophagy Contributes to Ischemic Preconditioning–Induced Neuroprotection in Mice with Ischemic Stroke via mTOR-ULK1 Pathway - Ying Zhang; Longhui Ma; Yi Yan; Li Zhao; Song Han; Di Wu; Cesar V. Borlongan; Junfa Li; Xunming Ji (Translational Stroke Research, 2023)

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Optimal design of a glider array for the observation of tropical cyclones - Yutong Sun; Dan Cheng; Shaoqiong Yang; Chenyi Luo; Di Tian; Han Zhang; Yanhui Wang (Progress in Oceanography, 2023)

Enriching Pt3 ensemble with isolated 3-fold hollow site by crystal-phase engineering of Pt3Fe single-nanoparticle for acetylene hydrogenation - Di Zhou; Guanghui Zhang; Yong Li; Shuang Liu; Shaobo Han; Yan Zhou; Wenjie Shen (Chemical Engineering Journal, 2023)

A novel diagnostic signature of circulating tsRNAs and miRNAs in esophageal squamous cell carcinoma detected with a microfluidic platform - Di Huang; Yujin Chu; Jiaoyan Qiu; Xiaoshuang Chen; Junhua Zhao; Yu Zhang; Shunjia Li; Yufeng Cheng; Han Shi; Lin Han; Jianbo Wang (Analytica Chimica Acta, 2023)

Multi-parameter cooperative optimization and solution method for regional integrated energy system - Di Wu; Ao Liu; Li Ma; Jiacheng Guo; Fanfan Ma; Zhonghe Han; Liming Wang (Sustainable Cities and Society, 2023)

Influence of circulation types on temporal and spatial variations of ozone in Beijing - Xiaowan Zhu; Jin Wu; Guiqian Tang; Lin Qiao; Tingting Han; Xiaomei Yin; Xiangxue Liu; Ziming Li; Yajun Xiong; Di He; Zhiqiang Ma (Journal of Environmental Sciences, 2023)

Study on pore structure characterization of strong diagenesis sandstones and the logging response characteristics in Tazhong area, Tarim Basin - Xidong Wang; Di Wang; Xin Li; Changcheng Han (Journal of Applied Geophysics, 2023)

Improvement of hydrolysis efficiency and interfacial properties of zein using nanoemulsions prepared by a low energy emulsification method - Jia-Ling He; Bo-Hao Liu; Han-Lin Zhang; Di Xu; Bao-Ming Shi; Ying-Hua Zhang (Food Bioscience, 2023)

Paintable graphene oxide-hybridized soy protein-based biogels for skin radioprotection - Daijun Zhou; Hui Liu; Lu Han; Di Liu; Xiaomei Liu; Qingyan Yan; Dan He; ZhiHui Li; Xiong Lu; Chaoyang Jiang; Dong Li (Chemical Engineering Journal, 2023)

Direct evolution of riboflavin kinase significantly enhance flavin mononucleotide synthesis by design and optimization of flavin mononucleotide riboswitch - Yuxuan Du; Xinyi Zhang; Hengwei Zhang; Rongshuai Zhu; Zhenqiang Zhao; Jin Han; Di Zhang; Xiaoling Zhang; Xian Zhang; Xuewei Pan; Jiajia You; Zhiming Rao (Bioresource Technology, 2023)

Phosphate adsorption on LDHs-biochar composite: Double-layer model for quantifying the contribution of ion exchange and ligand exchange - Shangkai Qiu; Mingyao Yuan; Mengmeng Li; Wenjia Han; Lisheng Zhang; Di Zhao; Xia Li; Keqiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2023)

Impact of biased technological progress on the total factor productivity of China's manufacturing industry: The driver of sustainable economic growth - Yi Qiu; Wanwan Han; Di Zeng (Journal of Cleaner Production, 2023)

The six-year biochar retention interacted with fertilizer addition alters the soil organic nitrogen supply capacity in bulk and rhizosphere soil - Di Wang; Yu Lan; Wenfu Chen; Xiaori Han; Suying Liu; Dianyun Cao; Xiaoyi Cheng; Qingyang Wang; Zengyi Zhan; Wanying He (Journal of Environmental Management, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

Deep learning approach for forecasting sea surface temperature response to tropical cyclones in the Western North Pacific - Han Zhang; Mengyuan Jing; Haoyu Zhang; Longjie Li; Yunxia Zheng; Jie Tang; Di Tian; Yanmin Zhu (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Correction to: Weak transgenerational effects of ancestral nitrogen and phosphorus availabilities on offspring phenotypes in Arabidopsis thaliana - Zhengbing Yan; Di Tian; Wenxuan Han; Chengjun Ji; Xinghui Hou; Yalong Guo; Jingyun Fang (Journal of Plant Research, 2023)

Weak transgenerational effects of ancestral nitrogen and phosphorus availabilities on offspring phenotypes in Arabidopsis thaliana - Zhengbing Yan; Di Tian; Wenxuan Han; Chengjun Ji; Xinghui Hou; Yalong Guo; Jingyun Fang (Journal of Plant Research, 2023)

Screening, structural characterization and anti-adipogenesis effect of a water-soluble polysaccharide from Lycium barbarum L. by an activity-oriented approach - Han Wang; Yunchun Li; Yunyun Dai; Ling Ma; Duolong Di; Jianfei Liu (Food Bioscience, 2023)

Numerical evaluation of the suitability of the equivalent porous medium model for characterizing the two-dimensional flow field in a fractured geologic medium - Lei Ma; Di Han; Jiazhong Qian; Di Gao; Haichun Ma; Yaping Deng; Xiaoliang Hou (Hydrogeology Journal, 2023)

Cytotoxicity, endocrine disrupting activity, and chemical analysis of 42 food contact silicone rubber products - Di Feng; Xueyan Li; Xiaojie Fan; Yifan Guo; Jingwei Zhang; Hang Yuan; Wenjuan Wang; Tingting Zhao; Tian Han (Science of The Total Environment, 2023)

UV-C irradiation maintains cell membrane integrity at wounds of potato tubers during healing by regulating ROS homeostasis and increasing antioxidant activity - Xuejiao Zhang; Xiaoyuan Zheng; Ye Han; Ruirui Yang; Qihui Wang; Di Gong; Yongcai Li; Dov Prusky; Yang Bi (Postharvest Biology and Technology, 2023)

Characteristics of changes in volatile organic compounds and microbial communities during the storage of pickles - Xi-han Sun; Xin Qi; Yu-di Han; Zhi-jun Guo; Cheng-bi Cui; Chang-qing Lin (Food Chemistry, 2023)

Genome-wide identification, expression analysis, and transcriptome analysis of the IAA gene family in Zoysia japonica - Zhuoxiong Yang; Di Dong; Zewen Qi; Chenyan Jia; Liebao Han; Yuehui Chao (Molecular Biology Reports, 2023)

Analysis of temporal and spatial variation characteristics of midlatitude summer nighttime anomaly in low and middle solar activity period - Jiandi Feng; Kaixin Wang; Wang Li; Baomin Han; Zhenzhen Zhao; Ting Zhang; Di Meng (Advances in Space Research, 2023)

Estimating industrial process emission and assessing carbon dioxide equivalent of perfluorooctanoic acid (PFOA) and its salts in China - Di Du; Yonglong Lu; Qifeng Li; Yunqiao Zhou; Tianzheng Cao; Haotian Cui; Guoxiang Han (Science of The Total Environment, 2023)

Evaluating ecotoxicological assays for comprehensive risk assessment of toxic metals present in industrial wastewaters in the Republic of Korea - Jihae Park; Kisik Shin; Hojun Lee; Soyeon Choi; Geonhee Kim; Stephen Depuydt; Jonas De Saeger; Philippe M. Heynderickx; Di Wu; Jana Asselman; Colin Janssen; Taejun Han (Science of The Total Environment, 2023)

Evaluating potential ecological risks of emerging toxic elements in lacustrine sediments: A case study in Lake Fuxian, China - Yixuan Han; Fan Xun; Cheng Zhao; Biao Li; Wenlei Luo; Muhua Feng; Di Xu; Peng Xing; Qinglong L. Wu (Environmental Pollution, 2023)

Surface-modified liquid metal nanocapsules derived multiple triboelectric composites for efficient energy harvesting and wearable self-powered sensing - Zihua Li; Bingang Xu; Jing Han; Di Tan; Junxian Huang; Yuanyuan Gao; Hong Fu (Chemical Engineering Journal, 2023)

QTL analysis of drought tolerance traits in rice during the vegetative growth period - Li Chen; Jing Ma; XiaoDing Ma; Di Cui; Bing Han; JianChang Sun; LongZhi Han (Euphytica, 2023)

Seasonal variations, source apportionment and dry deposition of chemical species of total suspended particulate in Pengjia Yu Island, East China Sea - Li Yu-Xiao; Liu Shu-Han; Luo Li; Yang Shu-Di; Lu Bin-Yu; Wang Chen; Hsu Shih-Chieh; Kao Shuh-Ji (Marine Pollution Bulletin, 2023)

Incorporating Surprisingly Popular Algorithm and Euclidean distance-based adaptive topology into PSO - Xuan Wu; Jizong Han; Di Wang; Pengyue Gao; Quanlong Cui; Liang Chen; Yanchun Liang; Han Huang; Heow Pueh Lee; Chunyan Miao; You Zhou; Chunguo Wu (Swarm and Evolutionary Computation, 2023)

The shared NDM-positive strains in the hospital and connecting aquatic environments - Huiyun Zou; Jingyi Han; Ling Zhao; Di Wang; Yanyu Guan; Tianle Wu; Xinjiao Hou; Hui Han; Xuewen Li (Science of The Total Environment, 2023)

Kalihiacyloxyamides A-H, α-acyloxy amide substituted kalihinane diterpenes isolated from the sponge Acanthella cavernosa collected in the South China Sea - Zhe Wang; Yueying Li; Xiao Han; Di Zhang; Huiyue Hou; Li Xiao; Guoqiang Li (Phytochemistry, 2023)

Genomic footprints of Kam Sweet Rice domestication indicate possible migration routes of the Dong people in China and provide resources for future rice breeding - Chunhui Liu; Tianyi Wang; Huicha Chen; Xiaoding Ma; Chengzhi Jiao; Di Cui; Bing Han; Xiaobing Li; Aixia Jiao; Renchao Ruan; Dayuan Xue; Yanjie Wang; et al. (Molecular Plant, 2023)

Multiscale fractures integrated equivalent porous media method for simulating flow and solute transport in fracture-matrix system - Lei Ma; Di Gao; Jiazhong Qian; Di Han; Kun Xing; Haichun Ma; Yaping Deng (Journal of Hydrology, 2023)

Key metabolites and mechanistic insights in forchlorfenuron controlling kiwifruit development - Yingying Bi; Chengkui Qiao; Lijun Han; Hanzhong Xie; Yanjun Xu; Di Wu; Ming Zhuang; Xinru Lv; Mengyuan Cao (Food Research International, 2023)

SWCNTs/Ag2Se film with superior bending resistance and enhanced thermoelectric performance via in situ compositing - Qin-Xue Hu; Wei-Di Liu; Li Zhang; Wei Sun; Han Gao; Xiao-Lei Shi; Yan-Ling Yang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2023)

Magnetic electrode configuration with polypyrrole-wrapped Ni/NiFe2O4 core–shell nanospheres to boost electrocatalytic water splitting - Lina Jia; Gaohui Du; Di Han; Yunting Wang; Wenqi Zhao; Qingmei Su; Shukai Ding; Bingshe Xu (Chemical Engineering Journal, 2023)

Urban park use and self-reported physical, mental, and social health during the COVID-19 pandemic: An on-site survey in Beijing, China - Di Lin; Yan Sun; Yue Yang; Yi Han; Chengyang Xu (Urban Forestry & Urban Greening, 2023)

Response of dissolved organic carbon in rainwater during extreme rainfall period in megacity: Status, potential source, and deposition flux - Jie Zeng; Guilin Han; Shitong Zhang; Xuhuan Xiao; Yikai Li; Xi Gao; Di Wang; Rui Qu (Sustainable Cities and Society, 2023)

Identifying greenhouse gas emission reduction potentials through large-scale photovoltaic-driven seawater desalination - Chao Ai; Lu Zhao; Di Song; Mengyao Han; Quan Shan; Siyuan Liu (Science of The Total Environment, 2023)

A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking - Chao Qi; Yueying Jin; Shengyu Cheng; Lei Di; Xin Wang; Minghui Zhang; Lingli Zhang; Xi-Ling Li; Yu Han; Qingkun Ma; Jun Zhe Min (Food Research International, 2023)

Comparative analysis of rice reveals insights into the mechanism of colored rice via widely targeted metabolomics - Lina Zhang; Di Cui; Xiaoding Ma; Bing Han; Longzhi Han (Food Chemistry, 2023)

Enhanced pre-sensitization in metal-free covalent organic frameworks promoting hydrogen peroxide photosynthesis - Xin Di; Ximeng Lv; Haozhen Wang; Fangshuai Chen; Shengyao Wang; Gengfeng Zheng; Bo Wang; Qing Han (Chemical Engineering Journal, 2023)

Gastrointestinal consequences of lipopolysaccharide-induced lung inflammation - Rachel M. McQuade; Methma Bandara; Shanti Diwakarla; Lauren Sahakian; Myat Noe Han; Maryam Al Thaalibi; Madeleine R. Di Natale; Marsha Tan; Kiera H. Harwood; Elena K. Schneider-Futschik; Andrew Jarnicki (Inflammation Research, 2023)
Background Respiratory inflammation is the body’s response to lung infection, trauma or hypersensitivity and is often accompanied by comorbidities, including gastrointestinal (GI) symptoms. Why respiratory inflammation is accompanied by GI dysfunction remains unclear. Here, we investigate the effect of lipopolysaccharide (LPS)-induced lung inflammation on intestinal barrier integrity, tight-junctions, enteric neurons and inflammatory marker expression. Methods Female C57bl/6 mice (6–8 weeks) were intratracheally administered LPS (5 µg) or sterile saline, and assessed after either 24 or 72 h. Total and differential cell counts in bronchoalveolar lavage fluid (BALF) were used to evaluate lung inflammation. Intestinal barrier integrity was assessed via cross sectional immunohistochemistry of tight junction markers claudin-1, claudin-4 and EpCAM. Changes in the enteric nervous system (ENS) and inflammation in the intestine were quantified immunohistochemically using neuronal markers Hu + and nNOS, glial markers GFAP and S100β and pan leukocyte marker CD45. Results Intratracheal LPS significantly increased the number of neutrophils in BALF at 24 and 72 h. These changes were associated with an increase in CD45 + cells in the ileal mucosa at 24 and 72 h, increased goblet cell expression at 24 h, and increased expression of EpCAM at 72 h. LPS had no effect on the expression of GFAP, S100β, nor the number of Hu + neurons or proportion of nNOS neurons in the myenteric plexus. Conclusions Intratracheal LPS administration induces inflammation in the ileum that is associated with enhanced expression of EpCAM, decreased claudin-4 expression and increased goblet cell density, these changes may contribute to systemic inflammation that is known to accompany many inflammatory diseases of the lung.

Whole cell of pure Clostridium butyricum CBT-1 from anaerobic bioreactor effectively hydrolyzes agro-food waste into biohydrogen - Tawaf Ali Shah; Li Zhihe; Li Zhiyu; Andong Zhang; Di Lu; Wang Fang; Han Xuan (Environmental Science and Pollution Research, 2023)

The global decline in the sensitivity of vegetation productivity to precipitation from 2001 to 2018 - Xiang Zeng; Zhongmin Hu; Anping Chen; Wenping Yuan; Guolong Hou; Daorui Han; Minqi Liang; Kai Di; Ruochen Cao; Dengnan Luo (Global Change Biology, 2022)
The sensitivity of vegetation productivity to precipitation ( S ppt ) is a key metric for understanding the variations in vegetation productivity under changing precipitation and predicting future changes in ecosystem functions. However, a comprehensive assessment of S ppt over all the global land is lacking. Here, we investigated spatial patterns and temporal changes of S ppt across the global land from 2001 to 2018 with multiple streams of satellite observations. We found consistent spatial patterns of S ppt with different satellite products: S ppt was highest in dry regions while low in humid regions. Grassland and shrubland showed the highest S ppt , and evergreen needle‐leaf forest and wetland showed the lowest. Temporally, S ppt showed a generally declining trend over the past two decades ( p S ppt was especially noticeable in North America and Europe, likely due to the increase in precipitation. In central Russia and Australia, however, S ppt showed an increasing trend. Biome‐wise, most ecosystem types exhibited significant decrease in S ppt , while grassland, evergreen broadleaf forest, and mixed forest showed slight increases or non‐significant changes in S ppt . Our finding of the overall decline in S ppt implies a potential stabilization mechanism for ecosystem productivity under climate change. However, the revealed S ppt increase for some regions and ecosystem types, in particular global grasslands, suggests that grasslands might be increasingly vulnerable to climatic variability with continuing global climate change.

Use of Hybrid Causal Logic Method for Preliminary Hazard Analysis of Maritime Autonomous Surface Ships - Di Zhang; Zhepeng Han; Kai Zhang; Jinfen Zhang; Mingyang Zhang; Fan Zhang (Journal of Marine Science and Engineering, 2022)
Recently, the safety issue of maritime autonomous surface ships (MASS) has become a hot topic. Preliminary hazard analysis of MASS can assist autonomous ship design and ensure safe and reliable operation. However, since MASS technology is still at its early stage, there are not enough data for comprehensive hazard analysis. Hence, this paper attempts to combine conventional ship data and MASS experiments to conduct a preliminary hazard analysis for autonomy level III MASS using the hybrid causal logic (HCL) method. Firstly, the hazardous scenario of autonomy level III MASS is developed using the event sequence diagram (ESD). Furthermore, the fault tree (FT) method is utilized to analyze mechanical events in ESD. The events involving human factors and related to MASS in the ESD are analyzed using Bayesian Belief Network (BBN). Finally, the accident probability of autonomy level III MASS is calculated in practice through historical data and a test ship with both an autonomous and a remote navigation mode in Wuhan and Nanjing, China. Moreover, the key influence factors are found, and the accident-causing event chains are identified, thus providing a reference for MASS design and safety assessment process. This process is applied to the preliminary hazard analysis of the test ship.

Response Process of Coastal Hypoxia to a Passing Typhoon in the East China Sea - Qicheng Meng; Feng Zhou; Xiao Ma; Jiliang Xuan; Han Zhang; Shuai Wang; Xiaobo Ni; Wenyan Zhang; Bin Wang; Dewang Li; Di Tian; Jia Li; et al. (Frontiers in Marine Science, 2022)
Details of the development of coastal hypoxia in response to the passage of Typhoon Bavi (2020) in the East China Sea were reconstructed by numerical modeling using a three-dimensional coupled physical–biogeochemical model. The model was validated via repeated surveys along a transect across a submerged river valley off the Changjiang Estuary before and after the passage of Typhoon Bavi. Before Bavi’s arrival, survey data indicated that the coastal hypoxia had formed off the Changjiang Estuary. However, the hypoxia was not eliminated but instead migrated and aggravated along the observed transect after the typhoon passage. This phenomenon cannot be attributed to the typhoon-induced mixing. Simulation results reveal that the observed development and spatial migration of hypoxia was mainly controlled by typhoon-induced oceanic advection. Results show that Bavi stimulated a regional quasi-barotropic cyclonic loop circulation and coastal downwelling reversing general summer circulation patterns. The onshore transport of the warmer shelf water and subsequent downwelling resulted in a warming of coastal water. The southward coastal current and downwelling induced by the typhoon also led to a migration of the hypoxic zone. Meanwhile, a massive transport of resuspended planktonic detritus from the steep inner shelf and the shallow Changjiang bank toward the submerged river valley occurred. This study reveals that the typhoon-driven currents can play an important role in the development of hypoxia and redistribution of deposited organic matter in coastal shelf seas, which may have both short- and long-term effects on the regional marine biogeochemical environment.

Early stem growth mutation alters metabolic flux changes enhance sesquiterpenoids biosynthesis in Atractylodes lancea (Thunb.) DC. - Di Wang; Fei Chen; Chun-Yan Wang; Xu Han; Chuan-Chao Dai (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

Effects of dissolved oxygen and nutrients from the Kuroshio on hypoxia off the Changjiang River estuary - Di Tian; Feng Zhou; Wenyan Zhang; Han Zhang; Xiao Ma; Xinyu Guo (Journal of Oceanology and Limnology, 2022)

The pH signalling transcription factor PacC modulate growth, development, stress response and pathogenicity of Trichothecium roseum - Bin Wang; Zhanhong Han; Di Gong; Xiaobin Xu; Yongcai Li; Edward Sionov; Dov Prusky; Yang Bi; Yuanyuan Zong (Environmental Microbiology, 2022)
Summary pH is one of the important environmental factors that affect the growth, development and pathogenicity of postharvest pathogen. The transcription factor PacC dominates the pH signal pathway. PacC in Trichothecium roseum showed three typical conserved zinc finger domains and closest homology to Fusarium graminearum . T. roseum increased the environmental pH both in vitro and in vivo . Expression patterns of TrpacC under different pH showed that at increasing pH from 3 to 5, the wild‐type (WT) strain induced the expression of TrPacC in parallel to increased fungal growth; however, TrPacC expression decline at higer pH than 5, while fungal growth continued to increase. Development of a Δ TrPacC mutant down‐regulated the expression of TrbrlA , TrabaA and TrwetA , reduced sporulation and delayed spore germination, resulting in smaller spores and sparse hyphae. Δ TrPacC mutant was sensitive to ionic stress, oxidative stress and cell wall integrity stress compared to the WT strain, especially the ionic stress. In addition, ∆ TrPacC mutant showed reduced pathogenicity to muskmelon and tomato fruits. Taken together, T. roseum is an alkalinizing fungus, and the acidic environment could induce TrPacC expression. TrPacC positively regulates fungal growth and development as well as pathogenicity showing effect on fungal response to different stresses.

Chemical constituent from the peel of Trichosanthes kirilowii Maxim and their NF-κB inhibitory activity - Xi Lei; Nan Li; Zisong Bai; Jingrui Di; Han Zhang; Pengzhi Dong; Peng Zhang (Natural Product Research, 2021)

Identification of QTLs for cold tolerance at the booting and flowering stages in rice (Oryza sativa L.) - Lina Zhang; Jianghong Tang; Di Cui; Cuifeng Tang; Xiaoding Ma; Xinxiang A; Bing Han; Guilan Cao; Zhengwu Zhao; Hee-Jong Koh; Longzhi Han (Euphytica, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Controlling pathogenic risks of water treatment biotechnologies at the source by genetic editing means - Jie Wu; Dong‐Feng Liu; Hui‐Hui Li; Di Min; Jia‐Qi Liu; Peng Xu; Wen‐Wei Li; Han‐Qing Yu; Yong‐Guan Zhu (Environmental Microbiology, 2021)
Summary Antimicrobial‐resistant pathogens in the environment and wastewater treatment systems, many of which are also important pollutant degraders and are difficult to control by traditional disinfection approaches, have become an unprecedented treat to ecological security and human health. Here, we propose the adoption of genetic editing techniques as a highly targeted, efficient and simple tool to control the risks of environmental pathogens at the source. An ‘all‐in‐one’ plasmid system was constructed in Aeromonas hydrophila to accurately identify and selectively inactivate multiple key virulence factor genes and antibiotic resistance genes via base editing, enabling significantly suppressed bacterial virulence and resistance without impairing their normal phenotype and pollutant‐degradation functions. Its safe application for bioaugmented treatment of synthetic textile wastewater was also demonstrated. This genetic‐editing technique may offer a promising solution to control the health risks of environmental microorganisms via targeted gene inactivation, thereby facilitating safer application of water treatment biotechnologies.

Three new diterpenoids from Euphorbia peplus - Yan-Ni Chen; Qing-Yun Lu; Dong-Mei Li; Ying-Yao Li; Xue-Xue Pu; Bo-Ting Li; Xiao-Han Tang; Hong-Yu Tang; Shuai Liu; Lei Yang; Yu Zhang; Ying-Tong Di; et al. (Natural Product Research, 2021)

Drivers of changes in soil properties during post-fire succession on Dahurian larch forest - Yuetai Weng; Zhaoguo Li; Sisheng Luo; Zhangwen Su; Xueying Di; Guang Yang; Hongzhou Yu; Dongdong Han (Journal of Soils and Sediments, 2021)

Triterpene saponins from tea seed pomace ( Camellia oleifera Abel) and their cytotoxic activity on MCF-7 cells in vitro - Xin-Fu Zhang; Ying-Ying Han; Tai-Mei Di; Li-Ping Gao; Tao Xia (Natural Product Research, 2021)

Single Exposure to Cocaine Impairs Reinforcement Learning by Potentiating the Activity of Neurons in the Direct Striatal Pathway in Mice - Zhijun Diao; Yuanyuan Di; Meilin Wu; Chenyang Zhai; Mengsi Kang; Yongfeng Li; Yingxun Liu; Chunling Wei; Qiaohua Zheng; Jing Han; Zhiqiang Liu; Yingfang Tian; et al. (Neuroscience Bulletin, 2021)

Screening and application of SSR markers related to seed storability traits in maize (Zea mays L.) - Xiaoyang Guo; Xiaohui Sun; Shan Liu; Chengxu Gong; Chenchen Feng; Xiao Han; Tingting Lv; Yu Zhou; Zhenhua Wang; Hong Di (Genetic Resources and Crop Evolution, 2021)

Exploring spatiotemporal variation characteristics of China’s industrial carbon emissions on the basis of multi-source data - Ying Fu; Wenbin Sun; Yi Zhao; Yahui Han; Di Yang; Yunbing Gao (Environmental Science and Pollution Research, 2021)

Tissue-specificity of RNA editing in plant: analysis of transcripts from three tobacco (Nicotiana tabacum) varieties - Jing Fang; Xiao-Han Jiang; Teng-Fei Wang; Xiu-Jun Zhang; Ai-Di Zhang (Plant Biotechnology Reports, 2021)

Changes in water‐soluble nitrogen and organic carbon in the post‐fire litter layer of Dahurian larch forests - Yuetai Weng; Guang Yang; Lixuan Wang; Xiankui Quan; Xueying Di; Hongzhou Yu; Dongdong Han (Plant and Soil, 2021)

Influence of polyethylene-microplastic on environmental behaviors of metals in soil - Ming Li; Dedong Wu; Di Wu; Hongliang Guo; Song Han (Environmental Science and Pollution Research, 2021)

Comparative analysis of genetic diversity of rice (Oryza sativa L.) varieties cultivated in different periods in China - Ruyu Tang; Di Cui; Jian Zhou; Wenqiu Li; Xiaoding Ma; Bing Han; Xiaohong Guo; Zhengwu Zhao; Longzhi Han (Genetic Resources and Crop Evolution, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Pressure Distribution and Deformation Control of Gob-Side Entry Retaining Formed by Roof Cutting Influenced by Abandoned Roadways - Xiaojie Yang; Lin Hou; Haojie Xue; Di Yuan; Jindong Cao; Zijie Han; Yubing Gao (Geotechnical and Geological Engineering, 2021)

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

Critical roles of macrophages in pressure overload-induced cardiac remodeling - Dan Yang; Han-Qing Liu; Fang-Yuan Liu; Nan Tang; Zhen Guo; Shu-Qing Ma; Peng An; Ming-Yu Wang; Hai-Ming Wu; Zheng Yang; Di Fan; Qi-Zhu Tang (Journal of Molecular Medicine, 2021)

Correction to: Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2020)

Disaster resilience assessment based on the spatial and temporal aggregation effects of earthquake-induced hazards - Bin Liu; Suyue Han; Hao Gong; Zhongli Zhou; Di Zhang (Environmental Science and Pollution Research, 2020)

Genetic removal of the CH1 exon leads to the production of hypofunctional heavy chain-only IgG2a in rats - Zhenrong Li; Ming Zhang; Shunan Zheng; Yu Song; Xueqian Cheng; Di Yu; Lijuan Du; Liming Ren; Haitang Han; Yaofeng Zhao (Transgenic Research, 2020)

DNA stable isotope probing revealed no incorporation of 13CO2 into comammox Nitrospira but ammonia-oxidizing archaea in a subtropical acid soil - Zi-Yang He; Ju-Pei Shen; Li-Mei Zhang; Hua-Jing Tian; Bing Han; Hong-Jie Di; Ji-Zheng He (Journal of Soils and Sediments, 2020)

The integrative regulatory network of circRNA and microRNA in keloid scarring - Jingpei Shi; Shuluan Yao; Pan Chen; Yuan Yang; Mengjiao Qian; Yi Han; Nan Wang; Yu Zhao; Yongjing He; Lechun Lyu; Di Lu (Molecular Biology Reports, 2020)

QTL analysis of main agronomic traits in rice under low temperature stress - Jianghong Tang; Xiaoding Ma; Di Cui; Bing Han; Leiyue Geng; Zhengwu Zhao; Yafei Li; Longzhi Han (Euphytica, 2019)

Rolling–sliding load decreases the loss of chondrocyte viability and the mechanical properties of cartilage explants preserved in vitro - Jianhong Qi; Chao Jin; Pengwei Qu; Lu Zhou; Di Xie; Hongqiang Song; Meng Men; Yunning Han; Caiyun Geng; Famin Cao; Yadi Wu (Cell and Tissue Banking, 2019)

Remediation of TCE-contaminated groundwater using KMnO4 oxidation: laboratory and field-scale studies - Zong-Han Yang; Jiun-Hau Ou; Cheng-Di Dong; Chiu-Wen Chen; Wei-Han Lin; Chih-Ming Kao (Environmental Science and Pollution Research, 2019)

A global database of paired leaf nitrogen and phosphorus concentrations of terrestrial plants - Di Tian; Jens Kattge; Yahan Chen; Wenxuan Han; Yongkai Luo; Jinsheng He; Huifeng Hu; Zhiyao Tang; Suhui Ma; Zhengbing Yan; Quanhong Lin; Bernhard Schmid; et al. (Ecology, 2019)
Nitrogen (N) and phosphorus (P) are essential components of the basic cell structure of plants. In particular, leaf N and P concentrations and their stoichiometric relationship largely determine the photosynthesis, growth, reproduction, and ecophysiological processes of plants. As important leaf functional traits, leaf N and P concentrations and their stoichiometric relationship play vital roles in indicating plant nutrient‐use strategies and their evolution in terrestrial ecosystems. They also influence physiological and ecological processes in leaves (e.g., growth rate and energy metabolism) and productivity (e.g., net primary production and net ecosystem production) at ecosystem level. However, the lack of a comprehensive data set containing paired leaf N and P concentration records has distinctly limited research on nutrient stoichiometry and leaf functional traits. Here, we provide a global database of paired records of leaf N and P concentrations. A total of 11,354 individual records were acquired spanning 1,291 sites worldwide, including 201 families, 1,265 genera, and 3,227 species. The records span a latitudinal range of 45.28 °S to 68.35 °N and a longitudinal range of 155.5 °W to 168.0 °E. The variables provided for each individual record are (1) geographical location (longitude, latitude, and altitude); (2) matched leaf N and P concentrations and N:P ratio; (3) taxonomic information (family, genera, and species); (4) life form (angiosperm/gymnosperm, monocotyledonous/dicotyledonous and woody plants/herbaceous plants; note that woody plants were further divided into coniferous, deciduous broad‐leaved, and evergreen broad‐leaved woody species and that herbaceous plants were further divided into annual and perennial species); (5) mean annual temperature ( MAT ) and mean annual precipitation ( MAP ); and (6) soil N and P concentrations and pH value in some records. To date, this database is the world's largest database of paired leaf N and P concentrations, which contains matched information of geographical location, environmental factors, and taxa. We believe that the database will play a fundamental and crucial part of ecological stoichiometric studies. There are no copyright restrictions. When using this database, we kindly request that you cite this article, respecting all the authors’ hard work during sample collection and data compilation.

Family-level leaf nitrogen and phosphorus stoichiometry of global terrestrial plants - Di Tian; Zhengbing Yan; Suhui Ma; Yuehong Ding; Yongkai Luo; Yahan Chen; Enzai Du; Wenxuan Han; Emoke Dalma Kovacs; Haihua Shen; Huifeng Hu; Jens Kattge; et al. (Science China Life Sciences, 2019)

High-resolution imaging of rhizosphere oxygen (O2) dynamics in Potamogeton crispus: effects of light, temperature and O2 content in overlying water - Chao Han; Jinghua Ren; Paul N. Williams; Fan Ke; Qiushi Shen; Zhaode Wang; Di Xu; Jun Luo (Plant and Soil, 2019)

CTHRC1 promotes M2-like macrophage recruitment and myometrial invasion in endometrial carcinoma by integrin-Akt signaling pathway - Lu-Ying Li; Ke-Min Yin; Yi-Han Bai; Zhi-Gang Zhang; Wen Di; Shu Zhang (Clinical & Experimental Metastasis, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Storage solution containing hydrogen improves the preservation effect of osteochondral allograft - Yunning Han; Pengwei Qu; Kaihong Zhang; Yikang Bi; Lu Zhou; Di Xie; Hongqiang Song; Jun Dong; Jianhong Qi (Cell and Tissue Banking, 2019)

The apple U-box E3 ubiquitin ligase MdPUB29 contributes to activate plant immune response to the fungal pathogen Botryosphaeria dothidea - Peng-Liang Han; Yuan-Hua Dong; Kai-Di Gu; Jian-Qiang Yu; Da-Gang Hu; Yu-Jin Hao (Planta, 2019)

The Role of Deimination in Regenerative Reprogramming of Neurons - Di Ding; Mabel Enriquez-Algeciras; Anddre Osmar Valdivia; Juan Torres; Cameron Pole; John W Thompson; Tsung-han Chou; Miguel Perez-Pinzon; Vittorio Porciatti; Susan Udin; Eric Nestler; Sanjoy K. Bhattacharya (Molecular Neurobiology, 2019)

Bioaccumulation of dichlorodiphenyltrichloroethanes (DDTs) in carp in a water/sediment microcosm: important role of sediment particulate matter and bioturbation - Shanshan Di; Jinling Diao; Xiangyun Wang; Peipei Qi; Zhiwei Wang; Hao Xu; Hu Zhang; Xinquan Wang; Jiajun Han (Environmental Science and Pollution Research, 2019)

FLA, which encodes a homolog of UBP, is required for chlorophyll accumulation and development of lemma and palea in rice - Xiaoding Ma; Jiani Zhang; Bing Han; Jianghong Tang; Di Cui; Longzhi Han (Plant Cell Reports, 2019)

The short-term effects of outdoor temperature on blood pressure among children and adolescents: finding from a large sample cross-sectional study in Suzhou, China - Jia Hu; Hui Shen; Chen-gang Teng; Di Han; Guang-ping Chu; Yi-kai Zhou; Qi Wang; Bo Wang; Jing-zhi Wu; Qi Xiao; Fang Liu; Hai-bing Yang (International Journal of Biometeorology, 2019)

Impacts of urbanization and agricultural development on observed changes in surface air temperature over mainland China from 1961 to 2006 - Songjun Han; Qiuhong Tang; Di Xu; Zhiyong Yang (Theoretical and Applied Climatology, 2019)

Tsmu solution improves rabbit osteochondral allograft preservation and transplantation outcome - Famin Cao; Jianhong Qi; Hongqiang Song; Di Xie; Lu Zhou; Yunning Han; Hao Li; Qi Wu; Jun Dong; Yanming Zhang (Cell and Tissue Banking, 2018)

Reliability of cartilage digestion and FDA–EB fluorescence staining for the detection of chondrocyte viability in osteochondral grafts - Jianhong Qi; Famin Cao; Yunning Han; Di Xie; Hongqiang Song; Bin Chen; Lu Zhou (Cell and Tissue Banking, 2018)

Neonatal Exposure to Low-Dose (1.2%) Sevoflurane Increases Rats’ Hippocampal Neurogenesis and Synaptic Plasticity in Later Life - Xi Chen; Xue Zhou; Lu Yang; Xu Miao; Di-Han Lu; Xiao-Yu Yang; Zhi-Bin Zhou; Wen-Bin Kang; Ke-Yu Chen; Li-Hua Zhou; Xia Feng (Neurotoxicity Research, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Nitrogen removal performance and microbial community of an enhanced multistage A/O biofilm reactor treating low-strength domestic wastewater - Han Chen; Ang Li; Qiao Wang; Di Cui; Chongwei Cui; Fang Ma (Biodegradation, 2018)

Biological data processing based on bio-processor unit (BPU), a new concept for next generation computational biology - Di Liu; Dongbo Bu; Tieliu Shi; Jianxiao Quan; Depeng Wang; Yongyong Shi; Xiao-Chen Bo; Wenbao Han (Science China Life Sciences, 2018)

Identification of quantitative trait loci associated with drought tolerance traits in rice (Oryza sativa L.) under PEG and field drought stress - Bing Han; Jiao Wang; Yafei Li; Xiaoding Ma; Sumin Jo; Di Cui; Yanjie Wang; Dongsoo Park; Youchun Song; Guilan Cao; Xingsheng Wang; Jianchang Sun; et al. (Euphytica, 2018)

Differential Inhibition of Nav1.7 and Neuropathic Pain by Hybridoma-Produced and Recombinant Monoclonal Antibodies that Target Nav1.7 - Sangsu Bang; Jiho Yoo; Xingrui Gong; Di Liu; Qingjian Han; Xin Luo; Wonseok Chang; Gang Chen; Sang-Taek Im; Yong Ho Kim; Judith A. Strong; Ma-Zhong Zhang; et al. (Neuroscience Bulletin, 2018)

Using poly-glutamic acid as soil-washing agent to remediate heavy metal-contaminated soils - Zong-Han Yang; Cheng-Di Dong; Chiu-Wen Chen; Yih-Terng Sheu; Chih-Ming Kao (Environmental Science and Pollution Research, 2018)

GmMYB58 and GmMYB205 are seed-specific activators for isoflavonoid biosynthesis in Glycine max - Xiaoyan Han; Qinggang Yin; Jinyue Liu; Wenbo Jiang; Shaokang Di; Yongzhen Pang (Plant Cell Reports, 2017)

Magnesium Sulfate Provides Neuroprotection in Eclampsia-Like Seizure Model by Ameliorating Neuroinflammation and Brain Edema - Xiaolan Li; Xinjia Han; Jinying Yang; Junjie Bao; Xiaodan Di; Guozheng Zhang; Huishu Liu (Molecular Neurobiology, 2017)

Observed near-surface atmospheric moisture content changes affected by irrigation development in Xinjiang, Northwest China - Songjun Han; Qiuhong Tang; Di Xu; Shaoli Wang; Zhiyong Yang (Theoretical and Applied Climatology, 2017)

Characterization of mitochondrial prohibitin from Boleophthalmus pectinirostris and evaluation of its possible role in spermatogenesis - Di Wang; Yong-Qiang Zhao; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2017)

Histochemical examination of systemic administration of eldecalcitol combined with guided bone regeneration for bone defect restoration in rats - Xiuchun Han; Juan Du; Di Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2017)

MiR-28 inhibits cardiomyocyte survival through suppressing PDK1/Akt/mTOR signaling - Rui-Yao Zhu; Di Zhang; Han-Dong Zou; Xiao-Shu Zuo; Qing-Shan Zhou; He Huang (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Preconditioning with VEGF Enhances Angiogenic and Neuroprotective Effects of Bone Marrow Mononuclear Cell Transplantation in a Rat Model of Chronic Cerebral Hypoperfusion - Jianping Wang; Xiaojie Fu; Lie Yu; Nan Li; Menghan Wang; Xi Liu; Di Zhang; Wei Han; Chenguang Zhou; Jian Wang (Molecular Neurobiology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Effect of cadmium exposure on antioxidant enzyme catalase in different tissues of Acrossocheilus fasciatus - Yong-Qiang Zhao; Guo-Di Liu; Cong-Cong Hou; Ying-Li Han; Jun-Quan Zhu (Molecular & Cellular Toxicology, 2016)

Molecular characterization of Sp110 gene in pigs - Li-zu Li; Qiu-shi Wang; Li-xin Han; Jin-kui Wang; Si-yu Shao; Liang Wang; Di Liu; Xiu-qin Yang (Molecular Genetics and Genomics, 2016)

Aging up-regulates ARA55 in stromal cells, inducing androgen-mediated prostate cancer cell proliferation and migration - Qingsong Zou; Di Cui; Shengjie Liang; Shujie Xia; Yifeng Jing; Bangmin Han (Journal of Molecular Histology, 2016)

Multifractal property and long-range cross-correlation behavior of particulate matters at urban traffic intersection in Shanghai - Hong-di He; Wei Pan; Wei-zhen Lu; Yu Xue; Guang-han Peng (Stochastic Environmental Research and Risk Assessment, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

A disparate subset of double-negative T cells contributes to the outcome of murine fulminant viral hepatitis via effector molecule fibrinogen-like protein 2 - Di Wu; Hongwu Wang; Weiming Yan; Tao Chen; Ming Wang; Meifang Han; Zeguang Wu; Xiaojing Wang; Guo Ai; Dong Xi; Guanxin Shen; Xiaoping Luo; et al. (Immunologic Research, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Occurrence and hydrogeochemical characteristics of high-fluoride groundwater in Xiji County, southern part of Ningxia Province, China - Chao Wei; Huaming Guo; Di Zhang; Yang Wu; Shuangbao Han; Yonghui An; Fucun Zhang (Environmental Geochemistry and Health, 2016)

Diachronic analysis of genetic diversity in rice landraces under on-farm conservation in Yunnan, China - Di Cui; Jinmei Li; Cuifeng Tang; Xinxiang A; Tengqiong Yu; Xiaoding Ma; Enlai Zhang; Guilan Cao; Furong Xu; Yongli Qiao; Luyuan Dai; Longzhi Han (Theoretical and Applied Genetics, 2016)

Improved SCS-CN Method Based on Storage and Depletion of Antecedent Daily Precipitation - Pingjin Jiao; Di Xu; Shaoli Wang; Yingduo Yu; Songjun Han (Water Resources Management, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Delivery of agricultural drought information via web services - Chunming Peng; Meixia Deng; Liping Di; Weiguo Han (Earth Science Informatics, 2015)

Connection between atmospheric latent energy and energy fluxes simulated by nine CMIP5 models - Bo Han; Shihua Lü; Ruiqing Li; Yinhuan Ao; Hao Chen; Yanhong Gao; Di Ma (Journal of Meteorological Research, 2015)

Enhanced lipid accumulation and biodiesel production by oleaginous Chlorella protothecoides under a structured heterotrophic-iron (II) induction strategy - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han (World Journal of Microbiology and Biotechnology, 2015)

Proteomics analysis for enhanced lipid accumulation in oleaginous Chlorella vulgaris under a heterotrophic-Na+ induction two-step regime - Yuqin Li; Jinxiu Mu; Di Chen; Hua Xu; Fangxin Han; Bo Feng; Hongyan Zeng (Biotechnology Letters, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Salidroside Ameliorates Cd-Induced Calcium Overload and Gap Junction Dysfunction in BRL 3A Rat Liver Cells - Hui Zou; Di Hu; Tao Han; Hongyan Zhao; Junze Xie; Xuezhong Liu; Yi Wang; Jianhong Gu; Yan Yuan; Jianchun Bian; Zongping Liu (Biological Trace Element Research, 2015)

First report of Hepatozoon (Apicomplexa: Adeleorina) from king ratsnakes (Elaphe carinata) in Shanghai, with description of a new species - Hongyu Han; Youling Wu; Hui Dong; Shunhai Zhu; Liujia Li; Qiping Zhao; Di Wu; Enle Pei; Yange Wang; Bing Huang (Acta Parasitologica, 2015)
Hepatozoon species are the most common hemoparasites of snakes. In this study, Hepatozoon parasites were examined for the first time in king rat snakes (Elaphe carinata) from Shanghai, China. All 10 snakes were found to be infected with Hepatozoon gamonts. The gamonts were folded back in a hook-wise fashion for about 3 μm at one end. Parasitemia levels ranged from 4-43 infected erythrocytes per 1,000 examined. The gamonts changed the morphology of the parasitized erythrocytes. Although the gamonts showed some distinct variations in both the parasite and its nucleus, phylogenetic analysis indicated that all the E. carinata in this study formed a monophyletic group, and were distinct from all other published Hepatozoon species. A new species, Hepatozoon chinensis, was proposed based on the molecular and morphologic evidence.

Similarities and differences of two evapotranspiration models with routinely measured meteorological variables: application to a cropland and grassland in northeast China - Songjun Han; Di Xu; Shaoli Wang; Zhiyong Yang (Theoretical and Applied Climatology, 2014)

Dishevelled-1 (Dvl-1) Protein: a Potential Participant of Oxidative Stress Induced by Selenium Deficiency - Han-dong Zhao; Mei-na Sun; Meng-di Li; Feng-lan Li; Hui Li (Biological Trace Element Research, 2014)

The histone deacetylase inhibitor vorinostat prevents TNFα-induced necroptosis by regulating multiple signaling pathways - Di Wang; Ming Zhao; Guozhu Chen; Xiang Cheng; Xiaoxi Han; Song Lin; Xuhui Zhang; Xiaodan Yu (Apoptosis, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Local Farmers’ Perceptions of Climate Change and Local Adaptive Strategies: A Case Study from the Middle Yarlung Zangbo River Valley, Tibet, China - Chunyan Li; Ya Tang; Han Luo; Baofeng Di; Liyun Zhang (Environmental Management, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Synthesis of novel 4-thiazolidione derivatives as antibacterial agents against drug-resistant Staphylococcus epidermidis - Dan Zhao; Huayong Liu; Likang Zheng; Guozhen He; Di Qu; Shiqing Han (Medicinal Chemistry Research, 2013)

Service-oriented approach for geospatial feature discovery - Peng Yue; Liping Di; Weiguo Han; Peisheng Zhao; Wenli Yang; Lianlian He (Earth Science Informatics, 2012)

CSMD1 exhibits antitumor activity in A375 melanoma cells through activation of the Smad pathway - Ming-Rui Tang; Yu-Xin Wang; Shu Guo; Si-Yuan Han; Di Wang (Apoptosis, 2012)

Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding Study of Platinum Originating from Dicycloplatin, a Novel Antitumor Supramolecule, in Rats and Dogs by ICP-MS - Di Zhao; Yongjie Zhang; Chunxiang Xu; Can Dong; Hui Lin; Lingli Zhang; Cuiyun Li; Shuangxia Ren; Xin Wang; Shuoye Yang; Deen Han; Xijing Chen (Biological Trace Element Research, 2012)

Elevated CO2 improves root growth and cadmium accumulation in the hyperaccumulator Sedum alfredii - Tingqiang Li; Zhenzhen Di; Xuan Han; Xiaoe Yang (Plant and Soil, 2012)

A New bis(rhodamine)-Based Fluorescent Chemosensor for Fe3+ - Xiaopo Chen; Huijie Hong; Rui Han; Di Zhang; Yong Ye; Yu-fen Zhao (Journal of Fluorescence, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Association of hypomethylation of LINE-1 repetitive element in blood leukocyte DNA with an increased risk of hepatocellular carcinoma - Jian-zhong Di; Xiao-dong Han; Wen-ye Gu; Yu Wang; Qi Zheng; Pin Zhang; Hui-min Wu; Zhong-zheng Zhu (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of SLCO1B1 polymorphisms on the pharmacokinetics and pharmacodynamics of repaglinide in healthy Chinese volunteers - Jiake He; Zhixia Qiu; Ning Li; Yang Yu; Yang Lu; Deen Han; Tingting Li; Di Zhao; Wei Sun; Fang Fang; Jianheng Zheng; Hongwei Fan; et al. (European Journal of Clinical Pharmacology, 2011)

Season- and age-associated telomerase activity in Ginkgo biloba L. - Han Song; Di Liu; Fenglan Li; Hai Lu (Molecular Biology Reports, 2011)

Impact assessment and protection of outstanding landscape integrity in a natural heritage site: Fairy valley, Kanas Nature Reserve, Xinjiang, China - Fang Han; Zhaoping Yang; Xinyu Liu; Feng Di (Journal of Mountain Science, 2011)

Change of season-specific telomere lengths in Ginkgo biloba L. - Han Song; Di Liu; Xin Chen; Zehua Ying; Bo Zhang; Fenglan Li; Hai Lu (Molecular Biology Reports, 2010)

Expression and purification of bioactive high-purity human midkine in Escherichia coli - Zhong-hui Zhang; Li-juan Du; Di Xiang; Shun-ying Zhu; Ming-yuan Wu; Hui-li Lu; Yan Yu; Wei Han (Journal of Zhejiang University-SCIENCE B, 2009)

Mesozoic paleogeography and tectonic evolution of South China Sea and adjacent areas in the context of Tethyan and Paleo‐Pacific interconnections - Di Zhou; Zhen Sun; Han‐zong Chen; He‐hua Xu; Wan‐yin Wang; Xiong Pang; Dong‐sheng Cai; Deng‐ke Hu (Island Arc, 2008)
During the Mesozoic era, the South China Sea and its environs were located at the south‐eastern margin of the Eurasian continent. There has been hot debate on the influences of Tethyan and Paleo‐Pacific tectonics to the Mesozoic evolution of the area. This paper compiles lithofacies maps of six time slices and discusses the paleogeographic and tectonic evolution of the area based on this compilation and other data on structural deformation and magmatism. In the Early Triassic, the Paleotethys Ocean extended eastward to the study area through the Song Da passage. Then a significant east–west differential evolution began. In the Late Triassic, the western area uplifted as a result of the collision between the Indosinian and South China blocks during the Indosinian orogeny, and the Song Da passage has closed since then. Meanwhile, a transgression of Paleo‐Pacific waters occurred in the eastern and south‐eastern portions of the area, forming the ‘East Guangdong–North‐west Borneo Sea’. In the Early Jurassic, seawater transgression was even more pronounced, resulting into the connection of this sea with the Mesotethys Ocean to the west. Large quantities of Tethyan water carrying Tethyan organisms entered the area. In the Middle Jurassic, a short‐lived transgression occurred in the eastern Mesotethys and resulted in the formation of the ‘Yunnan–Burma Sea’. The Late Jurassic to Early Cretaceous was the climax of the subduction of both the Mesotethys and Paleo‐Pacific towards the Eurasian continent. This led to the formation of the great ‘Circum South‐east Asia Subduction–Accretion Zone’ in the Middle or Late Cretaceous. This paper also presents various lines of evidence for a newly recognized segment of this Mesozoic subduction–accretion zone buried under Cenozoic sediments in the north‐eastern South China Sea.

Carrying capacity of marine region in Liaoning Province - Qianbin Di; Zenglin Han; Guichun Liu; Hongwei Chang (Chinese Geographical Science, 2007)

Comparative analysis of telomeric restriction fragment lengths in different tissues of Ginkgo biloba trees of different age - Di Liu; Nan Qiao; Han Song; Xin Hua; Juan Du; Hai Lu; Fenglan Li (Journal of Plant Research, 2007)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)